Metallocene catalyzed polyethylene and articles made therefrom

Solving the problem of insufficient surface smoothness of linear low-density polyethylene in a two-step extrusion process by using Ziegler-Natta catalysts and metallocene-catalyzed polyethylene blends, achieving better surface quality and roughness control.

CN119320526AActive Publication Date: 2025-01-17埃克森美孚(惠州)化工有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411172121.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2025-01-17
Estimated Expiration
2044-08-26

AI Technical Summary

Technical Problem

In the two-step extrusion process, linear low-density polyethylene (LLDPE) prepared based on Ziegler-Natta catalysts showed poor surface smoothness, affecting product quality.

Method used

Improved polyethylene blends by adjusting their melt index, density, molecular weight distribution, and composition distribution width index using blends containing Ziegler-Natta catalyst-catalyzed linear low-density polyethylene and metallocene-catalyzed polyethylene. surface quality of the object.

Benefits of technology

Relative to pure Ziegler-Natta catalyst-catalyzed LLDPE and pure metallocene-catalyzed polyethylene, the roughness grayscale of the polyethylene blends was reduced by 35-70% and 12-58% in the two-step extrusion process The optimal roughness grayscale standard deviation is achieved, significantly improving surface smoothness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320526A_ABST
    Figure CN119320526A_ABST
Patent Text Reader

Abstract

The present invention relates to a polyethylene blend comprising a Ziegler-Natta catalyst catalyzed linear low density polyethylene and a metallocene catalyzed polyethylene wherein the metallocene catalyzed polyethylene has a melt index (MI) in the range of from 0.1 g / 10 min to 30 g / 10 min, a density in the range of from 0.890 g / cm < 3 > to 0.940 g / cm < 3 >, a molecular weight distribution (MWD) in the range of from 2 to 12, and a compositional distribution width index in the range of from 10 to 50, the roughness gray level of the polyethylene blend is reduced by 35-70% relative to that of linear low density polyethylene catalyzed by a pure Ziegler-Natta catalyst, and / or is reduced by 12-58% relative to that of polyethylene catalyzed by pure metallocene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The disclosure of the present application relates to a polyethylene blend, comprising a linear low-density polyethylene catalyzed by a Ziegler-Natta catalyst and a metallocene-catalyzed polyethylene, wherein the metallocene-catalyzed polyethylene has a melt index (MI) of 0.1 g / 10 min to 30 g / 10 min and a density of 0.890 g / cm 3 Up to 0.940g / cm 3 , a molecular weight distribution (MWD) of 2 to 12, and a composition distribution width index of 10 to 50, wherein the composition distribution refers to the distribution of comonomers (short chain branches) in the molecules comprising the polyethylene polymer, and the roughness gray scale of the polyethylene blend is reduced by 35-70% relative to the linear low density polyethylene catalyzed by a pure Ziegler-Natta catalyst, and / or by 12-58% relative to the polyethylene catalyzed by a pure metallocene. In addition, the polyethylene blend achieves a roughness gray scale standard deviation (STD) of <11, preferably 7.5-3.5, and more preferably 6.5-4.5 in a two-step extrusion process. Background Art

[0002] For applications involving polyolefins, especially polyethylene blending, such as pipe extrusion, profile extrusion, etc., a two-step extrusion process is generally used. That is, the polyolefin polymer and other additives are first melt-mixed in a screw and then granulated and then these blend particles are further melt-plasticized by the screw and extruded into a pipe or profile. In these applications, surface quality is a very important consideration, especially for production scenarios with high extrusion line speeds. In such applications, linear low-density polyethylene ("LLDPE"), especially linear low-density polyethylene prepared by the Ziegler-Natta process, is a commonly used component.

[0003] Linear low density polyethylene ("LLDPE") is a substantially linear macromolecule composed of ethylene monomer units and alpha-olefin comonomer units. Typical comonomer units used commercially are derived from 1-butene, 1-hexene or 1-octene. LLDPE can be distinguished from conventional low density polyethylene ("LDPE") in many ways. Their respective manufacturing processes are different. LLDPE has essentially no detectable long chain branching per 1,000 carbon atoms, while conventional LDPE contains long chain branching. Relative to the molecular weight distribution (MWD) of LDPE, the MWD of LLDPE is narrower.

[0004] However, after the two-step extrusion process, the linear low-density polyethylene prepared based on the Ziegler-Natta process shows poor surface smoothness, so customers need to solve such problems and provide a technical solution to improve the surface smoothness.

[0005] WO94 / 12568A1 discloses the use of an effective amount of a polyolefin blend having a density greater than or equal to 0.900 g / cm 3 The low weight average molecular weight polyethylene, for example with a polydispersity index greater than 3.5, shows that improved surface properties are achieved after higher shear processing of the blend, thereby greatly eliminating or effectively minimizing the occurrence of surface distortion. The low weight average molecular weight polyethylene is used in an amount of about 30% to about 80% by weight.

[0006] US5,344,714A discloses a linear low density polyethylene film composite material formed by coextrusion and without melt fracture, comprising A) a layer of linear low density polyethylene (LLDPE) blended with polystyrene, which constitutes at least 70% by weight of the composite material, wherein the blend contains 0.5 to 5% by weight of polystyrene; and B) a second thin layer constituting less than 30% by weight of the composite material and comprising a resin selected from high density polyethylene, low density polyethylene and mixtures thereof.

[0007] US5,925,448A discloses a film prepared in a two-step extrusion process, the film comprising a blend of component (i) a linear low density polyethylene and component (ii) an in-situ blend of a copolymer of ethylene and one or more α-olefins having 3 to 8 carbon atoms, wherein the weight ratio of component (i) to component (ii) is in the range of about 0.01:1 to about 6:1; (b) the blend is extruded under extrusion conditions at a die rate in the range of about 6 to about 20 pounds per hour per inch of die circumference and at a die gap of about 0.020 to about 0.075 inches; and (c) the film does not substantially exhibit melt fracture.

[0008] US2022 / 0176592A1 discloses a method for extruding a melt of a linear low-density polyethylene (LLDPE) to form an LLDPE extrudate without surface melt fracture, the method comprising heating the melt of the polyethylene to 200.0 to 260.0°C; and -1 ) and under a shear stress greater than 0.41 megapascals (MPa), thereby forming an LLDPE extrudate without surface melt fracture; and cutting the LLDPE extrudate into pellets having a surface without surface melt fracture. Summary of the invention

[0009] In one embodiment, the present invention provides a polyethylene blend comprising a linear low density polyethylene catalyzed by a Ziegler-Natta catalyst and a metallocene-catalyzed polyethylene, wherein the metallocene-catalyzed polyethylene has a melt index (MI) of 0.1 g / 10 min to 30 g / 10 min, a density of 0.890 g / cm 3Up to 0.940g / cm 3 , molecular weight distribution (MWD) of 2 to 12, and composition distribution width index of 10 to 50, the roughness gray scale of the polyethylene blend is reduced by 35-70% relative to the linear low density polyethylene catalyzed by pure Ziegler-Natta catalyst, and / or reduced by 12-58% relative to the polyethylene catalyzed by pure metallocene. In addition, the polyethylene blend achieves a roughness gray scale STD of <11, preferably 7.5-3.5, and more preferably 6.5-4.5 in a two-step extrusion process.

[0010] In another class of embodiments, the present invention provides the use of the metallocene-catalyzed polyethylene to improve the surface quality, particularly the surface smoothness, of a linear low density polyethylene catalyzed by a Ziegler-Natta catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 is the surface quality of pure LL7042 after the two-step extrusion process.

[0012] Figure 2 is the surface quality of LL7042+25% S9333 after the two-step extrusion process.

[0013] Figure 3 is the surface quality of LL7042+50% S9333 after the two-step extrusion process.

[0014] Figure 4 is the surface quality of LL7042+75% S9333 after the two-step extrusion process.

[0015] Figure 5 is the surface quality of pure S9333 after the two-step extrusion process.

[0016] Figure 6 is a schematic diagram describing gray value measurement. DETAILED DESCRIPTION OF THE INVENTION

[0018] Before disclosing and describing the compounds, components, compositions and / or methods of the present invention, it should be understood that, unless otherwise indicated, the present invention is not limited to specific compounds, components, compositions, reactants, reaction conditions, ligands, metallocene structures, catalyst structures, or the like, as these may vary unless otherwise specified. It should also be understood that the various terms used herein are only for the purpose of describing specific embodiments and are not intended to be limiting.

[0019] In several embodiments of the present invention, the present disclosure relates to a polyethylene blend comprising a linear low density polyethylene catalyzed by a Ziegler-Natta catalyst and a metallocene-catalyzed polyethylene, wherein the metallocene-catalyzed polyethylene has a melt index (MI) of 0.1 g / 10 min to 30 g / 10 min, a density of 0.890 g / cm 3 Up to 0.940g / cm 3 , molecular weight distribution (MWD) of 2 to 12, and composition distribution width index of 10 to 50, the roughness gray scale of the polyethylene blend is reduced by 35-70% relative to the linear low density polyethylene catalyzed by pure Ziegler-Natta catalyst, and / or reduced by 12-58% relative to the polyethylene catalyzed by pure metallocene. In addition, the polyethylene blend achieves a roughness gray scale STD of <11, preferably 7.5-3.5, and more preferably 6.5-4.5 in a two-step extrusion process.

[0020] Linear Low Density Polyethylene Catalyzed by Ziegler-Natta Catalyst

[0021] Ziegler-Natta catalyst prepared linear low density polyethylene is also referred to as ZN-LLDPE. ZN-LLDPE is made by copolymerizing ethylene with an alpha-olefin comonomer in the presence of a Ziegler-Natta catalyst such as TiCl4 disposed on a particulate MgCl2 support. Ziegler-Natta catalysts are well known and include Ziegler-Natta catalyst components and systems of column 12, lines 13 to 49; column 12, lines 58 to column 13, line 25; and cocatalysts of US7,122,607B2 of Robert O. Hagerty et al., column 13, lines 31 to column 14, line 28. Copolymerization processes are generally well known and can be slurry phase, solution phase or gas phase processes. Suitable gas phase processes are described, for example, in US Pat. No. 7,122,607 B2 at column 25, line 59 to column 26, line 21 and at column 33, line 32 to column 35, line 56.

[0022] The α-olefin comonomer used to prepare ZN-LLDPE can be (C3-C 20 ) α-olefins, alternatively (C 11 -C 20 ) α-olefins, alternatively (C3 to C 10)α-olefin, alternatively (C4-C8)α-olefin, alternatively 1-butene or 1-hexene, alternatively 1-butene, alternatively 1-hexene, alternatively 1-octene. ZN-LLDPE can be characterized by its monomer content (i.e., ethylene monomer content) and comonomer content (i.e., α-olefin comonomer content). The α-olefin comonomer unit of ZN-LLDPE can be a 1-butene comonomer unit, alternatively a 1-hexene comonomer unit, alternatively a 1-octene comonomer unit.

[0023] The density of ZN-LLDPE can be from 0.905 to 0.930 g / cm 3 , alternatively 0.915 to 0.926 g / cm 3 , alternatively 0.920 to 0.926 g / cm 3 , alternatively 0.918±0.003g / cm 3 , alternatively 0.918±0.002g / cm 3 , alternatively 0.918±0.001g / cm 3 , alternatively 0.918 g / cm 3 , all measured according to ASTM D792-13. The melt index I2 of the ZN-LLDPE may be 0.5 to 2.5 g / 10 min, alternatively 0.5 to 2.04 g / 10 min, alternatively 0.5 to 1.99 g / 10 min, alternatively 0.6 to 1.4 g / 10 min, alternatively 0.9 to 1.1 g / 10 min, all measured according to ASTM D1238-04. The Mw of the ZN-LLDPE may be 1,000 to 1,000,000 grams per mole (g / mol), alternatively 10,000 to 500,000 g / mol, alternatively 20,000 to 200,000 g / mol.

[0024] Examples of ZN-LLDPE are commercially available and include LL1001 from EXXONMOBIL, LLDPEDFDA7042 from Sinopec, DOW LLDPEDFDA 7047NT 7; FORMOLENE L42022B from Taiwan Plastics; HIFOR LF1021 and NOVAPOL TD-9022 from Westlake Chemical Corporation; and MARFLEX 7109 polyethylene from Chevron Phillips.

[0025] Metallocene-catalyzed polyethylene

[0026] definition

[0027] For purposes of this invention and the claims thereto, the numbering scheme for the Periodic Table Groups shall be in accordance with the new notation for the IUPAC Periodic Table of the Elements.

[0028] As used herein, "olefin polymerization catalyst(s)" refers to any catalyst capable of coordination polymerization addition, typically an organometallic complex or compound, wherein successive monomers are added into the monomer chain at an organometallic active center.

[0029] The terms "substituent," "radical," "group," and "moiety" are used interchangeably.

[0030] When used herein and unless otherwise specified, the term “C n ” refers to hydrocarbon(s) containing n carbon atoms(s) per molecule, where n is a positive integer.

[0031] As used herein and unless otherwise specified, the term "hydrocarbon" refers to a class of compounds containing hydrogen bonded to carbon, and encompasses (i) saturated hydrocarbon compounds, (ii) unsaturated hydrocarbon compounds, and (iii) mixtures of hydrocarbon compounds (saturated and / or unsaturated), including mixtures of hydrocarbon compounds having different values ​​of n.

[0032] The terms "hydrocarbyl radical", "hydrocarbyl", "hydrocarbyl group", "alkyl radical" and "alkyl" are used interchangeably throughout the document. Similarly, the terms "group", "substituent" and "group" are also used interchangeably in this document. For the purpose of this disclosure, a "hydrocarbyl group" is defined as a C1-C 100 A substituted hydrocarbon radical is a hydrocarbon radical which may be linear, branched or cyclic and, when cyclic, aromatic or non-aromatic. Examples of such radicals include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, pentyl, isopentyl, hexyl, octyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cyclooctyl, and the like, including substituted analogs thereof. A substituted hydrocarbon radical is one in which at least one hydrogen atom of the hydrocarbon radical has been replaced with at least one heteroatom or heteroatom-containing group, such as a halogen (e.g., Br, Cl, F, or I) or at least one functional group such as NR*2, OR*, SeR*, TeR*, PR*2, AsR*2, SbR*2, SR*, BR*2, SiR*3, GeR*3, SnR*3, PbR*3, and the like, or a group in which at least one heteroatom has been inserted into the hydrocarbon ring.

[0033] As used herein and unless otherwise specified, the term "alkyl" refers to a group containing 1 to 12 carbon atoms (i.e., C1-C 12 Alkyl), especially 1-8 carbon atoms (ie, C 1- C8 alkyl), especially 1-6 carbon atoms (i.e., C1-C6 alkyl), especially 1-4 carbon atoms (i.e., C1-C4 alkyl) saturated hydrocarbon groups. Examples of alkyl groups include, but are not limited to methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, decyl, and the like. The alkyl group may be linear, branched or cyclic. "Alkyl" is intended to encompass all structural isomeric forms of alkyl. For example, propyl, when used herein, encompasses n-propyl and isopropyl; butyl encompasses n-butyl, sec-butyl, isobutyl and tert-butyl, and the like. When used herein, "C1 alkyl" refers to methyl (-CH3), "C2 alkyl" refers to ethyl (-CH2CH3), "C3 alkyl" refers to propyl (-CH2CH2CH3) and "C4 alkyl" refers to butyl (e.g., -CH2CH2CH2CH3, -(CH3)CHCH2CH3, -CH2CH(CH3)2, etc.). Additionally, when used herein, "Me" refers to methyl, "Et" refers to ethyl, "i-Pr" refers to isopropyl, "t-Bu" refers to tert-butyl, and "Np" refers to neopentyl.

[0034] As used herein and unless otherwise specified, the term "alkylene" refers to a divalent alkyl moiety containing 1 to 12 carbon atoms in length (i.e., C1-C 12 Alkylene) does not mean that the alkylene moiety is connected to the rest of the molecule at both ends of the alkyl unit. For example, alkylene includes, but is not limited to -CH2-, -CH2CH2-, -CH(CH3)CH2-, -CH2CH2CH2-, etc. Alkylene can be linear or branched.

[0035] As used herein and unless otherwise specified, the term "alkenyl" refers to an alkylene group containing 2 to 12 carbon atoms (i.e., C2-C 12 The term "alkenyl" refers to an unsaturated hydrocarbon group having 2 to 8 carbon atoms (i.e., C2-C8 alkenyl), especially 2 to 6 carbon atoms (i.e., C2-C6 alkenyl) and containing one or more (e.g., 2, 3, etc.) carbon-carbon double bonds. The alkenyl group can be linear, branched or cyclic. Examples of alkenyl groups include, but are not limited to, ethenyl (vinyl), 2-propenyl, 3-propenyl, 1,4-pentadienyl, 1,4-butadienyl, 1-butenyl, 2-butenyl and 3-butenyl. "Alkenyl" is intended to encompass all structural isomeric forms of alkenyl. For example, butenyl encompasses 1,4-butadienyl, 1-butenyl, 2-butenyl and 3-butenyl, etc.

[0036] As used herein and unless otherwise specified, the term "alkenylene" refers to a divalent alkenyl moiety containing from 2 to about 12 carbon atoms in length (i.e., C2-C 12 The term "alkenylene" refers to an alkylene moiety that is attached to the rest of the molecule at both ends of the alkyl unit. For example, alkenylene includes, but is not limited to, -CH=CH-, -CH=CHCH2-, -CH=CH=CH-, -CH2CH2CH=CHCH2-, etc. Alkenylene can be linear or branched.

[0037] As used herein and unless otherwise specified, the term "alkynyl" refers to a alkylene group containing 2 to 12 carbon atoms (i.e., C2-C 12 Alkynyl) is an unsaturated hydrocarbon group having 2 to 8 carbon atoms (i.e., C2-C8 alkynyl), especially 2 to 6 carbon atoms (i.e., C2-C6 alkynyl) and containing one or more (e.g., 2, 3, etc.) carbon-carbon triple bonds. Alkynyl groups can be linear, branched or cyclic. Examples of alkynyl groups include, but are not limited to, ethynyl, 1-propynyl, 2-butynyl and 1,3-butadiynyl. "Alkynyl" is intended to encompass all structural isomeric forms of alkynyl. For example, butynyl encompasses 2-butynyl and 1,3-butadiynyl, and propynyl encompasses 1-propynyl and 2-propynyl (propargyl).

[0038] As used herein and unless otherwise specified, the term "alkynylene" refers to a divalent alkynyl moiety containing from 2 to about 12 carbon atoms in length (i.e., C2-C 12 Alkyne) refers to the alkylene moiety connected to the rest of the molecule at both ends of the alkyl unit. For example, alkenylene includes, but is not limited to -C≡C-, -C≡CCH2-, -C≡CCH2C≡C-, -CH2CH2C≡CCH2-. Alkyne can be linear or branched.

[0039] As used herein and unless otherwise specified, the term "alkoxy" refers to an --O--alkyl group containing 1 to about 10 carbon atoms. Alkoxy groups can be straight or branched. Non-limiting examples include methoxy, ethoxy, propoxy, butoxy, isobutoxy, tert-butoxy, pentyloxy, and hexyloxy. "C1 alkoxy" refers to methoxy, "C2 alkoxy" refers to ethoxy, "C3 alkoxy" refers to propoxy, and "C4 alkoxy" refers to butoxy. In addition, when used herein, "OMe" refers to methoxy, and "OEt" refers to ethoxy.

[0040] As used herein and unless otherwise specified, the term "aromatic" refers to a hydrocarbon having an exosomatic conjugated π system and containing 5 to 20 carbon atoms (aromatic C5-C 20 Hydrocarbons), especially 5-12 carbon atoms (aromatic C5-C 12Hydrocarbons), especially 5-10 carbon atoms (aromatic C5-C 12 Exemplary aromatic compounds include, but are not limited to, benzene, toluene, xylene, mesitylene, ethylbenzene, cumene, naphthalene, methylnaphthalene, dimethylnaphthalene, ethylnaphthalene, acenaphthylene, anthracene, phenanthrene, tetraphene, tetracene, benzanthracene, fluoranthene, pyrene, (chrysene), triphenylene, etc., and combinations thereof.

[0041] Unless otherwise indicated, when isomers of an alkyl, alkenyl, alkoxy or aryl group are listed (e.g., n-butyl, isobutyl, sec-butyl and tert-butyl), one member of the group (e.g., n-butyl) should explicitly disclose the remaining isomers in the class (e.g., isobutyl, sec-butyl and tert-butyl). Similarly, a reference to an alkyl, alkenyl, alkoxy or aryl group without specifying a particular isomer (e.g., butyl) specifically discloses all isomers (e.g., n-butyl, isobutyl, sec-butyl and tert-butyl).

[0042] As used herein, the term "hydroxy" refers to an -OH group.

[0043] As used herein, "oxygenate" refers to a saturated, unsaturated or polycyclic cyclized hydrocarbon group containing 1 to 40 carbon atoms and further containing one or more oxygen heteroatoms.

[0044] As used herein, "alkylaluminum adduct" refers to the reaction product of an aluminum alkyl and / or aluminoxane and a quenching agent, such as water and / or methanol.

[0045] "Olefins", or "olefins", are linear, branched or cyclic compounds of carbon and hydrogen having at least one double bond. For purposes of this specification and the claims appended thereto, when a polymer or copolymer is referred to as containing an olefin, the olefin present in such polymer or copolymer is the polymerized form of the olefin. For example, when a copolymer is said to have an "ethylene" content of 35 wt% to 55 wt%, it is understood that the monomer units in the copolymer are derived from ethylene in the polymerization reaction and the derived units are present at 35 wt% to 55 wt%, based on the weight of the copolymer.

[0046] A "polymer" has two or more monomeric units that are the same or different. A "homopolymer" is a polymer containing the same monomeric units. A "copolymer" is a polymer having two or more monomeric units that are different or distinct from each other. A "terpolymer" is a polymer having three monomeric units that are different or distinct from each other. "Different" or "different" as used in reference to monomeric units indicates that the monomeric units differ from each other by at least one atom or are isomerically different. Thus, the definition of copolymer as used herein includes terpolymers and the like. An "ethylene polymer" or "ethylene copolymer" is a polymer or copolymer comprising at least 50 mol% ethylene-derived units, a "propylene polymer" or "propylene copolymer" is a polymer or copolymer comprising at least 50 mol% propylene-derived units, and so forth.

[0047] As used herein, "polymerizable conditions" refers to those conditions, including temperature, pressure, reactant concentrations, optional solvents / diluents, reactant mixing / addition parameters, and other conditions selected by the skilled artisan to facilitate the reaction of one or more olefin monomers when contacted with an activated olefin polymerization catalyst to produce the desired polyolefin polymer, typically via coordination polymerization, within at least one polymerization reactor.

[0048] The term "continuous" refers to a system that operates without interruption or stopping. For example, a continuous process for making a polymer would be one in which the reactants are continuously introduced into one or more reactors and the polymer product is continuously withdrawn.

[0049] A "catalyst composition" or "catalyst system" is a combination of at least one catalyst compound, a support material, an optional activator, and an optional co-activator. For purposes of this invention and the claims thereto, when a catalyst system or composition is described as comprising neutral stable forms of components, it will be understood by those skilled in the art that the ionic form of the components is the form that reacts with the monomers to produce the polymer. When it is used to describe such a combination after activation, it refers to the support, the activating complex, and the activator or other charge balancing moieties. The transition metal compound may be neutral, as in a procatalyst, or a charged species with a counterion, as in an activated catalyst system.

[0050] Coordination polymerization is an addition polymerization in which successive monomers are added into or at an organometallic active center to produce and / or grow a polymer chain.

[0051] The terms "cocatalyst" and "activator" are used interchangeably herein and are defined as any compound capable of activating any of the above catalyst compounds by converting the neutral catalyst compound into a catalytically active catalyst compound cation.

[0052] The term "contact product" or "combined product" is used herein to describe a composition in which the components are contacted together in any order, in any manner, and for any length of time. For example, the components may be contacted by blending or mixing. In addition, contact of any component may be performed in the presence or absence of any other component of the composition described herein. The combination of additional materials or components may be performed by any suitable method. In addition, the term "contact product" includes mixtures, blends, solutions, slurries, reaction products, etc., or combinations thereof. Although a "contact product" may include a reaction product, it is not required that the corresponding components react with each other or in the manner inferred. Similarly, the term "contact" is used herein to refer to materials that may be blended, mixed, slurried, dissolved, reacted, treated, or otherwise contacted in some other manner.

[0053] "BOCD" refers to a broad orthogonal composition distribution in which the comonomers of the copolymer are primarily incorporated in high molecular weight chains or species of the polyolefin polymer or composition. For example, the distribution of short chain branches can be measured using temperature rising elution fractionation (TREF) in conjunction with a light scattering (LS) detector to determine the weight average molecular weight of the molecules eluted from the TREF column at a given temperature. The combination of TREF and LS (TREF-LS) yields information about the width of the composition distribution and whether the comonomer content increases, decreases, or is uniform along chains of different molecular weights of the polymer chain. BOCD has been described, for example, in U.S. Pat. Nos. 8,378,043, col. 3, line 34 to col. 4, line 19; and 8,476,392, lines 43 to col. 16, line 54.

[0054] The width of the composition distribution is given by T 75 -T 25 Value characterization, where T 25 is the temperature at which 25% of the eluted polymer is obtained in the TREF experiments described herein, T 75 is the temperature at which 75% of the eluted polymer is obtained in the TREF experiment described herein. The composition distribution is further determined by F 80 The F value is the fraction of polymer that elutes below 80°C in the TREF-LS experiment described herein. 80 Higher values ​​indicate a higher proportion of comonomer in the polymer molecule. 60 / M 90 Value definition, where M 60 is the molecular weight of the polymer fraction eluted at 60 °C in the TREF-LS experiment, M 90 is the molecular weight of the polymer fraction eluting at 90°C in the TREF-LS experiment described herein.

[0055] In one class of embodiments, the polymers described herein may have a75 -T 25 A BOCD value of 1 or greater, 2.0 or greater, 2.5 or greater, 4.0 or greater, 5.0 or greater, 7.0 or greater, 10.0 or greater, 11.5 or greater, 15.0 or greater, 17.5 or greater, 20.0 or greater, or 25.0 or greater, 30.0 or greater, 35.0 or greater, 40.0 or greater, or 45.0 or greater, where T 25 is the temperature at which 25% of the eluted polymer is obtained in the TREF experiment described herein, T 75 is the temperature at which 75% of the eluted polymer is obtained.

[0056] The polymers described herein may further have a characteristic that M 60 / M 90 A BOCD value of 1.5 or greater, 2.0 or greater, 2.25 or greater, 2.50 or greater, 3.0 or greater, 3.5 or greater, 4.0 or greater, 4.5 or greater, or 5.0 or greater, where M 60 is the molecular weight of the polymer fraction eluting at 60°C in the TREF-LS experiment described herein, M 90 is the molecular weight of the polymer fraction eluting at 90°C in the TREF-LS experiment described herein.

[0057] In addition, the polymers described herein may further have a 80 The value is 1% or greater, 2% or greater, 3% or greater, 4% or greater, 5% or greater, 6% or greater, 7% or greater, 10% or greater, 11% or greater, 12% or greater, or 15% or greater of BOCD, where F 80 It is the proportion of polymer eluting at a temperature below 80°C.

[0058] Olefin polymerization catalyst

[0059] Metallocene catalysts

[0060] In one class of embodiments, the catalyst system can be a mixed metallocene catalyst system (ie, comprising more than one catalyst) and comprises two or more of the following catalysts, such as a catalyst represented by formula (A):

[0061]

[0062] in:

[0063] M is Hf or Zr;

[0064] Each R 1 , R 2 and R 4are independently hydrogen, alkoxide or C1-C 40 Substituted or unsubstituted hydrocarbon group (preferably C1-C 20 substituted or unsubstituted hydrocarbon group);

[0065] R 3 are independently hydrogen, alkoxy or C1-C 40 Substituted or unsubstituted hydrocarbon group (preferably C1-C 20 substituted or unsubstituted hydrocarbon), or -R 20 -SiR'3 or -R 20 -CR'3, where R 20 is hydrogen, or a C1-C4 hydrocarbon group, each R' is independently C1-C 20 Substituted or unsubstituted hydrocarbon, provided that at least one R' is not H;

[0066] Each R 7 , R 8 and R 10 are independently hydrogen, alkoxy or C1-C 40 Substituted or unsubstituted hydrocarbon group (preferably C1-C 20 substituted or unsubstituted hydrocarbon group);

[0067] R 9 Yes-R 20 -SiR'3 or -R 20 -CR'3 where R 20 is hydrogen or C1-C4 hydrocarbon (preferably R 20 is CH2), each R' is independently C1-C 20 Substituted or unsubstituted hydrocarbon, (preferably R' is alkyl, such as Me, or aryl, such as phenyl), provided that at least one R' is not H, or 2 R' are not H, or 3 R' are not H;

[0068] T is a bridging group, such as CR 21 R 22 , where R 21 and R 22 are independently hydrogen, halogen or C1-C 20 A hydrocarbon group (eg, a linear hydrocarbon group), a substituted hydrocarbon group, optionally, R 21 and R 22 joined to form a substituted or unsubstituted, saturated, partially unsaturated or aromatic, cyclic or polycyclic substituent, optionally, R 21 and R 22 are the same or different; and

[0069] Each X is independently a monovalent anionic ligand, or two Xs are joined and bonded to the metal atom to form a metallocycle ring, or two Xs are joined to form a chelating ligand, a diene ligand or an alkylidene ligand (preferably, a halogen or C1-C 12 alkyl or aryl, such as Cl, Me, Et, Ph).

[0070] In a preferred embodiment of the present invention, M is Hf, or M is Zr.

[0071] In a preferred embodiment of the present invention, each R 1 , R 2 and R 4 are independently hydrogen, or substituted C1-C 12 Hydrocarbon or unsubstituted C1-C 12 The hydrocarbon group is preferably hydrogen, methyl, ethyl, propyl, butyl, pentyl, hexyl or isomers thereof.

[0072] In a preferred embodiment of the present invention, each R 3 are independently hydrogen, or substituted C1-C 12 Hydrocarbon or unsubstituted C1-C 12 Hydrocarbyl, preferably hydrogen, methyl, ethyl, propyl, butyl, pentyl, hexyl or isomers thereof or R 3 Yes-R 20 -SiR'3 or -R 20 -CR'3, where R 20 is a C1-C4 hydrocarbon group (preferably methyl, ethyl, propyl, butyl), R' is a C1-C 20 Substituted or unsubstituted hydrocarbon group, preferably substituted C1-C 12 Hydrocarbon or unsubstituted C1-C 12 The hydrocarbon group is preferably a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group or an isomer thereof.

[0073] In a preferred embodiment of the present invention, each R 7 , R 8 and R 10 are independently hydrogen, or substituted C1-C 12 Hydrocarbon or unsubstituted C1-C 12 The hydrocarbon group is preferably hydrogen, methyl, ethyl, propyl, butyl, pentyl, hexyl or isomers thereof.

[0074] In a preferred embodiment of the present invention, R 9 Yes-R 20 -SiR'3 or -R 20 -CR'3, where R 20is a C1-C4 hydrocarbon group (preferably methyl, ethyl, propyl, butyl), R' is a C1-C 20 Substituted or unsubstituted hydrocarbon group, preferably substituted C1-C 12 Hydrocarbon or unsubstituted C1-C 12 The hydrocarbon group is preferably a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group or an isomer thereof.

[0075] Or, R 9 and optionally, R 3 Independently -R 20 -CMe3 or -R 20 -SiMe3, where R 20 It is a C1-C4 hydrocarbon group (preferably methyl, ethyl, propyl, butyl), preferably -CH2-CMe3 or -CH2-SiMe3.

[0076] Alternatively, each X may independently be a halide, a hydride, an alkyl, an alkenyl, or an aralkyl.

[0077] Alternatively, each X is independently selected from a hydrocarbon group containing 1 to 20 carbon atoms, an aryl group, a hydrogen group, an amino group (amide), an alkoxy group, a sulfide group, a phosphide group, a halogen group, a diene group, an amine, a phosphine group, an ether and a combination thereof (two X groups may form a part of a fused ring or a ring system), preferably, each X is independently selected from a halogen group, an aryl group and a C1-C5 alkyl group, preferably, each X is a phenyl group, a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a bromo group or a chloro group.

[0078] Preferably, T is a bridging group comprising at least one element of Group 13, 14, 15 or 16, especially boron or an element of Group 14, 15 or 16. Examples of suitable bridging groups include P(=S)R', P(=Se)R', P(=O)R', R'2C, R'2Si, R'2Ge, R'2CCR'2, R'2CCR'2CR'2, R'2CCR'2CR'2CR'2, R'C=CR', R'C=CR'CR'2, R'2CCR'=CR'CR'2, R'C=CR'CR'=CR', R'C=CR'CR'2CR'2, R'2CSiR'2, R'2SiSiR'2, R'2 SiOSiR'2, R'2CSiR'2CR'2, R'2SiCR'2SiR'2, R'C=CR'SiR'2, R'2CGeR'2, R'2GeGeR'2, R'2CGeR'2CR'2, R'2Ge CR'2GeR'2, R'2SiGeR'2, R'C=CR'GeR'2, R'B, R'2C-BR', R'2C-BR'-CR'2, R'2C-O-CR'2, R'2CR'2C-O-CR'2CR'2 , R'2C-O-CR'2CR'2, R'2C-O-CR'=CR', R'2C-S-CR'2, R'2CR'2C-S-CR'2CR'2, R'2C-S-CR'2CR'2, R'2C-S-CR'= CR', R'2C-Se-CR'2, R'2CR'2C-Se-CR'2CR'2, R'2C-Se-CR'2CR'2, R'2C-Se-CR'=CR', R'2C-N=CR', R'2C-NR'-C R'2, R'2C-NR'-CR'2CR'2, R'2C-NR'-CR'=CR', R'2CR'2C-NR'-CR'2CR'2, R'2C-P=CR', R'2C-PR'-CR'2, O, S, Se, Te, NR', PR', AsR', SbR', OO, SS, R'N-NR', R'P-PR', OS, O-NR', O-PR', S-NR', S-PR' and R'N-PR', wherein R' is hydrogen or a C1-C 20The alkyl, substituted alkyl, halocarbyl, substituted halocarbyl, silylcarbyl or germylcarbyl substituents are optionally joined to form substituted or unsubstituted, saturated, partially unsaturated or aromatic, cyclic or polycyclic substituents. Preferred examples of the bridging group T include CH2, CH2CH2, SiMe2, SiPh2, SiMePh, Si(CH2)3, Si(CH2)4, O, S, NPh, PPh, NMe, PMe, NEt, NPr, NBu, PEt, PPr, Me2SiOSiMe2 and PBu.

[0079] In a preferred embodiment of the present invention, in any embodiment of any formula described herein, T is represented by the formula R a 2J or (R a 2J)2, where J is C, Si or Ge, and each R a are independently hydrogen, halogen, C1-C 20 A hydrocarbon group (e.g., methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl or dodecyl) or a C1-C 20 substituted hydrocarbon group, and two R a A cyclic structure including an aromatic, partially saturated or saturated cyclic or condensed ring system can be formed. Preferably, T is a carbon or silicon-containing bridging group, such as a dialkylsilyl group, preferably T is selected from CH2, CH2CH2, C(CH3)2, SiMe2, SiPh2, SiMePh, silylcyclobutyl (Si(CH2)3), (Ph)2C, (p-(Et)3SiPh)2C, Me2SiOSiMe2 and cyclopentasilylene (Si(CH2)4).

[0080] In a preferred embodiment of the present invention, the molar ratio of racemic to meso in the catalyst compound is 1:1-100:1, preferably 5:1-90:1, preferably 7:1-80:1, preferably 5:1 or greater, or 7:1 or greater, or 20:1 or greater, or 30:1 or greater or 50:1 or greater. In one embodiment of the invention, the metallocene catalyst comprises greater than 55 mol% of racemic isomers, or greater than 60 mol% of racemic isomers, or greater than 65 mol% of racemic isomers, or greater than 70 mol% of racemic isomers, or greater than 75 mol% of racemic isomers, or greater than 80 mol% of racemic isomers, or greater than 85 mol% of racemic isomers, or greater than 90 mol% of racemic isomers, or greater than 92 mol% of racemic isomers, or greater than 95 mol% of racemic isomers, or greater than 97 mol% of racemic isomers, based on the total amount of racemic and meso isomers formed, if any. In a specific embodiment of the invention, the metallocene transition metal compound formed consists essentially of the racemic isomer.

[0081] The amount of racemic and meso isomers was determined by proton NMR. The spectra were collected at 23 °C using a 400 MHz Bruker spectrometer with deuterated dichloromethane and a 5 mm probe. 1 H NMR data. (It should be noted that some examples herein may use deuterated benzene, but for claims purposes, dichloromethane should be used.) Data were recorded using a maximum pulse width of 45°, 5 seconds between pulses, and signal averaging of 16 transients. The spectrum was normalized to protonated dichloromethane in deuterated dichloromethane, which is expected to show a peak at 5.32 ppm.

[0082] Catalyst compounds particularly useful in the present invention include one or more of the following: racemic / meso Me2Si(Me3SiCH2Cp)2HfMe2; racemic Me2Si(Me3SiCH2Cp)2HfMe2; racemic / meso Ph2Si(Me3SiCH2Cp)2HfMe2; racemic / meso (CH2)3Si(Me3SiCH2Cp)2HfMe2; racemic / meso (CH2)4Si(Me3SiCH2Cp)2HfMe2; racemic / meso (C6F5)2Si(Me3SiCH2Cp)2HfMe2; racemic / meso (CH2)3Si(Me3SiCH2Cp)2 ZrMe2; racemic / meso Me2Ge(Me3SiCH2Cp)2HfMe2; racemic / meso Me2Si(Me2PhSiCH2Cp)2HfMe2; racemic / meso Ph2Si(Me2PhSiCH2Cp)2HfMe2; Me2Si(Me4Cp)(Me2PhSiCH2Cp)HfMe2; racemic / meso (CH2)3Si(Me2PhSiCH2Cp)2HfMe2; racemic / meso (CH2)4Si(Me2PhSiCH2Cp)2HfMe2; racemic / meso (C6F5)2Si(Me2PhSiCH2Cp)2HfMe2; racemic / meso Meso-Me2Ge(Me2PhSiCH2Cp)2HfMe2; Meso-Me2Si(MePh2SiCH2Cp)2HfMe2; Meso-Ph2Si(MePh2SiCH2Cp)2HfMe2; Meso-Me2Si(MePh2SiCH2Cp)2ZrMe2; Meso-Me2(CH2)3Si(MePh2SiCH2Cp)2HfMe2; Meso-Me2(CH2)4Si(MePh2SiCH2Cp)2HfMe2; Meso-Me2(C6F5)2Si(MePh2SiCH2Cp)2HfMe2; Meso-Me2Ge(Me2 ... e(MePh2SiCH2Cp)2HfMe2; racemic / meso Me2Si(Ph3SiCH2Cp)2HfMe2; racemic / meso Ph2Si(Ph3SiCH2Cp)2HfMe2; racemic / meso Me2Si(Ph3SiCH2Cp)2ZrMe2; racemic / meso (CH2)3Si(Ph3SiCH2Cp)2HfMe2; racemic / meso (CH2)4Si(Ph3SiCH2Cp)2HfMe2; racemic / meso (C6F5)2Si(Ph3SiCH2Cp)2HfMe2; racemic / meso Me2Ge(Ph3SiCH2Cp)2HfMe2;Racemic / meso Me2Si(Cy3SiCH2Cp)2HfMe2; Racemic Me2Si(Cy3SiCH2Cp)2HfMe2; Racemic / meso Ph2Si(Cy3SiCH2Cp)2HfMe2; Racemic / meso Me2Si(Cy3SiCH2Cp)2ZrMe2; Racemic / meso (CH2)3Si(Cy3SiCH2Cp)2HfMe2; Racemic / meso (CH2)4Si(Cy3SiCH2Cp)2HfMe2; Racemic / meso (C6F5)2Si(Cy3SiCH2Cp)2HfMe2; Racemic / meso Me2Ge(Cy3SiCH2 Cp)2HfMe2; racemic / meso Me2Si(Cy2MeSiCH2Cp)2HfMe2; racemic / meso Ph2Si(Cy2MeSiCH2Cp)2HfMe2; Me2Si(Me4Cp)(Cy2MeSiCH2Cp)HfMe2; racemic / meso (CH2)3Si(Cy2MeSiCH2Cp)2HfMe2; racemic / meso (CH2)4Si(Cy2MeSiCH2Cp)2HfMe2; racemic / meso (C6F5)2Si(Cy2MeSiCH2Cp)2HfMe2; racemic / meso Me2Ge(Cy2MeSiCH2Cp)2 HfMe2; racemic / meso Me2Si(CyMe2SiCH2Cp)2HfMe2; racemic / meso Ph2Si(CyMe2SiCH2Cp)2HfMe2; racemic / meso (CH2)3Si(CyMe2SiCH2Cp)2HfMe2; racemic / meso (CH2)4Si(CyMe2SiCH2Cp)2HfMe2; racemic / meso (C6F5)2Si(CyMe2SiCH2Cp)2HfMe2; racemic / meso Me2Ge(CyMe2SiCH2Cp)2HfMe2; racemic / meso Me2Si(Cy2PhSiCH2Cp)2HfM e2; racemic / meso Ph2Si(Cy2PhSiCH2Cp)2HfMe2; racemic / meso (CH2)3Si(Cy2PhSiCH2Cp)2HfMe2; racemic / meso (CH2)4Si(Cy2PhSiCH2Cp)2HfMe2; racemic / meso (C6F5)2Si(Cy2PhSiCH2Cp)2HfMe2; racemic / meso Me2Ge(Cy2PhSiCH2Cp)2HfMe2; racemic / meso Me2Si(CyPh2SiCH2Cp)2HfMe2; racemic / meso Ph2Si(CyPh2SiCH2Cp)2HfMe2;rac / meso (CH2)3Si(CyPh2SiCH2Cp)2HfMe2; rac / meso (CH2)4Si(CyPh2SiCH2Cp)2HfMe2; rac / meso (C6F5)2Si(CyPh2SiCH2Cp)2HfMe2; and rac / meso Me2Ge(CyPh2SiCH2Cp)2HfMe2. ;

[0083] In a preferred embodiment, in any of the methods described herein, one catalyst compound is used, e.g., the catalyst compounds are not different. For purposes of the present invention, a catalyst compound is considered different if it differs from another by at least one atom. For example, "bis-indenyl zirconium dichloride" is different from "(indenyl)(2-methylindenyl)zirconium dichloride," which is different from "(indenyl)(2-methylindenyl)hafnium dichloride." Catalyst compounds that differ only by isomers are considered the same for purposes of the present invention, e.g., rac-dimethyl-dimethylsilyl-bis(2-methyl-4-phenylindenyl)hafnium is considered the same as meso-dimethyl-dimethylsilyl-bis(2-methyl-4-phenylindenyl)hafnium.

[0084] Other useful olefin polymerization catalysts include metallocene catalyst compounds represented by the following formula (B):

[0085] T y Cp m M 6 G n X 5 q (B),

[0086] wherein each Cp is independently a cyclopentadienyl group which may be substituted or unsubstituted (e.g., cyclopentadiene, indene or fluorene), M 6 is a Group 4 transition metal, such as titanium, zirconium, or hafnium, and G is represented by the formula JR* z A heteroatom group represented by wherein J is N, P, O or S, and R* is C1-C 20 hydrocarbon group, z is 1 or 2, T is a bridging group, y is 0 or 1, X 5 is a leaving group (e.g., a halide, a hydrogen group, an alkyl group, an alkenyl group, or an aralkyl group), and m=1 or 2, n=0, 1, 2, or 3, q=0, 1, 2, or 3, and the sum of m+n+q is equal to the oxidation state of the transition metal. See, for example, WO 2016 / 094843.

[0087] In one embodiment, each Cp is cyclopentadiene, indene or fluorene which may be substituted or unsubstituted, and each M 6 is titanium, zirconium or hafnium, each X 5R* may be methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, cyclooctyl, cyclododecyl, decyl, undecyl, dodecyl, adamantyl or an isomer thereof.

[0088] In yet another embodiment, the one or more olefin polymerization catalysts may comprise one or more of the following metallocene catalysts: bis(tetrahydroindenyl)HfMe2; bis(1-butyl, 3-methylcyclopentadienyl)ZrCl2; bis-(n-butylcyclopentadienyl)ZrCl2; (dimethylsilyl)2Obis(indenyl)ZrCl2; dimethylsilyl(3-(3-methylbutyl)cyclopentadienyl)(2,3,4,5-tetramethylcyclopentadienyl)ZrCl2; dimethylsilyl·bis(tetrahydroindenyl)ZrCl2; dimethylsilyl-(3-phenyl-indenyl)(tetramethyl Cyclopentadienyl) ZrCl2; Dimethylsilyl (3-neopentylcyclopentadienyl) (tetramethylcyclopentadienyl) HfCl2; Tetramethyldisilylbis (4-(3,5-di-tert-butylphenyl)-indenyl) ZrCl2; Cyclopentadienyl (1,3-diphenylcyclopentadienyl) ZrCl2; Dichloro bis (cyclopentadienyl) zirconium; Dichloro bis (pentamethylcyclopentadienyl) zirconium; Dimethyl bis (pentamethylcyclopentadienyl) zirconium; Dichloro bis (pentamethylcyclopentadienyl) zirconium Bis(pentamethylcyclopentadienyl)hafnium chloride; Bis(pentamethylcyclopentadienyl)zirconium dimethyl; Bis(1-methyl-3-n-butylcyclopentadienyl)zirconium dichloride; Bis(1-methyl-3-n-butylcyclopentadienyl)zirconium dimethyl; Bis(1-methyl-3-n-butylcyclopentadienyl)hafnium dichloride; Bis(1-methyl-3-n-butylcyclopentadienyl)zirconium dimethyl; Bis(indenyl)zirconium dichloride; Bis(indenyl)zirconium dimethyl; Bis(1-methyl-3-n-butylcyclopentadienyl)zirconium dichloride ·Bis(tetrahydro-1-indenyl)zirconium; dimethyl·bis(tetrahydro-1-indenyl)zirconium; dichloro·dimethylsilyl·bis(tetrahydroindenyl)zirconium; dimethyl·dimethylsilyl·bis(tetrahydroindenyl)zirconium; dimethylsilyl·bis(indenyl)zirconium dichloride; dimethyl·dimethylsilyl (bisindenyl) zirconium; dichloro·dimethylsilyl·bis(cyclopentadienyl) zirconium; or dimethyl·dimethylsilyl·bis(cyclopentadienyl) zirconium.

[0089] In another embodiment, the one or more olefin polymerization catalyst compounds may comprise a first metallocene catalyst and a second metallocene catalyst independently selected from the group consisting of: SiMe2(Me4Cp)(cC 12 N)TiMe2 and bis(1-Bu,3-Me-Cp)ZrCl2;SiMe2(Me4Cp)(cC 12N)TiMe2 and (SiMe2) bis(indenyl)ZrCl2; SiMe2(Me4Cp)(cC 12 N)TiMe2 and (SiMe2)2O bis(indenyl)ZrCl2; SiMe2(Me4Cp)(cC 12 N)TiMe2 and SiMe2)2O bis(indenyl)ZrMe2; SiMe2(Me4Cp)(cC 12 N)TiMe2 and SiMe2(3-neopentylCp)((Me4Cp)HfCl2; SiMe2(Me4Cp)(cC 12 N)TiMe2 and SiMe2(3-neopentylcyclopentadienyl)(Me4Cp)HfMe2; SiMe2(Me4Cp)(1-adamantylamino)TiMe2 and bis(1-Bu,3-MeCp)ZrCl2; and SiMe2(Me4Cp)(1-tert-butylamino)TiMe2 and bis(1-Bu,3-MeCp)ZrCl2.

[0090] In one class of embodiments, the one or more metallocene catalysts may include (4-propyl, 1,2-dimethylcyclopentadienyl)(cyclopentadienyl) hafnium dichloride; (tetramethylcyclopentadienyl)(propylcyclopentadienyl) hafnium dimethyl; (tetramethylcyclopentadienyl)(propylcyclopentadienyl) zirconium dimethyl; (3,4-dipropyl, 1,2-dimethylcyclopentadienyl)(cyclopentadienyl) hafnium dimethyl; (propylcyclopentadienyl)(methylcyclopentadienyl) hafnium dimethyl dichloro·silacyclopentyl(tetramethylcyclopentadienyl)(cyclopentadienyl)zirconium; dichloro·dimethylsilyl(tetramethylcyclopentadienyl)(3-(1-hexenyl)cyclopentadienyl)zirconium; or dimethyl·dimethylsilyl(tetramethylcyclopentadienyl)(3-trimethylsilylmethylcyclopentadienyl) hafnium.

[0091] In another class of embodiments, the one or more metallocene catalysts may include bis(cyclopentadienyl)zirconium dichloride, bis(cyclopentadienyl)zirconium dimethyl, bis(n-butylcyclopentadienyl)zirconium dichloride, bis(n-butylcyclopentadienyl)zirconium dimethyl, bis(pentamethylcyclopentadienyl)zirconium dichloride, bis(pentamethylcyclopentadienyl)zirconium dimethyl, bis(pentamethylcyclopentadienyl)hafnium dichloride, bis(pentamethylcyclopentadienyl)zirconium dimethyl, bis(1-methyl-3- zirconium dichloride, bis(1-methyl-3-phenylcyclopentadienyl) zirconium dichloride, bis(1-methyl-3-phenylcyclopentadienyl) zirconium dichloride, bis(1-methyl-3-phenylcyclopentadienyl) zirconium dichloride, bis(1-methyl-3-n-butylcyclopentadienyl) hafnium dichloride, bis(1-methyl-3-n-butylcyclopentadienyl) zirconium dichloride, bis(indenyl) zirconium dichloride, bis(tetrahydro-1-indenyl) zirconium dichloride , dimethyl·bis(tetrahydro-1-indenyl)zirconium, dichloro·(n-propylcyclopentadienyl)(pentamethylcyclopentadienyl)zirconium, dimethyl·(n-propylcyclopentadienyl)(pentamethylcyclopentadienyl)zirconium, dichloro·racemic / meso-(1-ethylindenyl)zirconium, dichloro·racemic / meso-(1-ethylindenyl)zirconium, dichloro·racemic / meso-(1-methylindenyl)zirconium, dichloro·racemic / meso-(1-methylindenyl)zirconium, dichloro·racemic / meso-(1-methylindenyl)zirconium -(1-propylindenyl)zirconium, dimethyl·racemic / meso-(1-propylindenyl)zirconium, dichloro·racemic / meso-(1-butylindenyl)zirconium, dimethyl·racemic / meso-(1-butylindenyl)zirconium, dichloro·meso-(1-ethylindenyl)zirconium, dimethyl·meso-(1-ethylindenyl)zirconium, dichloro·(1-methylindenyl)(pentamethylcyclopentadienyl)zirconium, dimethyl·(1-methylindenyl)(pentamethylcyclopentadienyl)zirconium or a combination thereof.

[0092] In yet another class of embodiments, the one or more metallocene catalysts may include rac / meso-(1-ethylindenyl) zirconium dichloride, rac / meso-(1-ethylindenyl) zirconium dimethyl, rac / meso-(1-methylindenyl) zirconium dichloride, rac / meso-(1-methylindenyl) zirconium dimethyl, rac / meso-(1-propylindenyl) zirconium dichloride, rac / meso-(1-ethylindenyl) zirconium dimethyl, -(1-propylindenyl)zirconium, dichloro·racemic / meso-(1-butylindenyl)zirconium, dimethyl·racemic / meso-(1-butylindenyl)zirconium, dichloro·meso-(1-ethylindenyl)zirconium, dimethyl·meso-(1-ethylindenyl)zirconium, dichloro·(1-methylindenyl)(pentamethylcyclopentadienyl)zirconium, dimethyl·(1-methylindenyl)(pentamethylcyclopentadienyl)zirconium or a combination thereof.

[0093] One or more of the above or following metallocene catalysts can be used by a mixed catalyst system, also known as a dual catalyst system, which comprises, for example, two or three metallocene catalysts or any catalyst described herein or known in the art that can be used for olefin polymerization. They can be co-loaded, i.e. arranged on the same carrier material, optionally and additionally, separately (with or without carrier) or together in different combinations and ratios injected into reactor (one or more) to "trim" or regulate polymer product performance according to its target specification. This method is very suitable for controlling polymer product performance and ensuring uniformity in the mass production of polyolefin polymers.

[0094] For example, a catalyst combination such as rac-ethylene-bis(indenyl)zirconium dichloride and diphenylmethylene{η 5 -[3-(Penten-4-yl)cyclopentadien-1-ylidene]}[η 5 -(2,7-di-tert-butylfluoren-9-ylidene)] zirconium complex, and other catalysts disclosed in U.S. Pat. No. 9,181,370 can be used in a catalyst system or a mixed catalyst system, sometimes also referred to as a dual catalyst system if only two catalysts are used. In another example, Me2Si(H4Ind)2ZrCl2 and (Me5Cp)PrCpZrCl2, and (Cp)IndZrCl2 and meso-O(Me2SiInd)2ZrCl2 can be used in a mixed catalyst system and other catalysts disclosed in U.S. Pat. No. 6,828,394. In yet another example, catalysts represented by "MTE-A" and "MTE-B" as disclosed in U.S. Pat. No. 9,181,369 can be used in a mixed catalyst system.

[0095] In another class of embodiments, the following catalysts may be used in the mixed catalyst system: dichlorophenyl-3-butenylmethylidene (η5 -cyclopentadienyl)(η 5 -9,2-7-di-tert-butylfluorenyl)zirconium dichloride, bis(indenyl)zirconium dichloride, diphenylmethylene{η 5 -[3-(Penten-4-yl)cyclopentadien-1-ylidene]}[η 5 -(2,7-di-tert-butylfluoren-9-ylidene)]hafnium, [dichloro·[η 5 -1-(propylene-2-yl)indenyl][η 5 -n-butylcyclopentadienyl] zirconium dichloride, racemic-ethylene-bis(indenyl) zirconium dichloride, diphenylmethylene{η 5 -[3-(Penten-4-yl)cyclopentadien-1-ylidene]}[η 5

[0013] zirconium-(2,7-di-tert-butylfluoren-9-ylidene)], and other catalysts disclosed in U.S. Pat. No. 9,006,367, or any catalyst disclosed in U.S. Pat. No. 9,217,049, such as those represented by the following structure:

[0096]

[0097]

[0098] Activator

[0099] The catalyst composition can be combined with an activator in any manner in the art, including loading them for use in slurry or gas phase polymerization. An activator is typically a compound that can activate any of the above-mentioned catalyst compounds by converting a neutral metal compound into a catalytically active metal compound cation. Non-limiting activators include, for example, aluminoxanes, alkylaluminums, ionizing activators (which can be neutral or ionic), and conventional types of cocatalysts. Preferred activators typically include aluminoxane compounds, modified aluminoxane compounds, and ionizing anion precursor compounds that capture reactive, σ-bonded metal ligands, thereby cationizing the metal compound and providing non-coordinating or weakly coordinating anions that balance the charge.

[0100] Aluminoxane Activator

[0101] Aluminoxane activators are used as activators in the catalyst compositions described herein. Aluminoxanes are generally 1 )-O-subunit oligomer compound, wherein R 1It is an alkyl group. Examples of aluminoxanes include methylaluminoxane (MAO), modified methylaluminoxane (MMAO), ethylaluminoxane and isobutylaluminoxane. Alkylaluminoxanes and modified alkylaluminoxanes are suitable as catalyst activators, especially when the extractable ligand is an alkyl, halide, alkoxy or amino group. Mixtures of different aluminoxanes and modified aluminoxanes can also be used. Visually transparent methylaluminoxane can be preferably used. Turbid or gelled aluminoxane can be filtered to prepare a transparent solution or a transparent aluminoxane can be decanted from the turbid solution. Useful aluminoxanes are modified methylaluminoxane (MMAO) cocatalyst 3A type (commercially available from Akzo Chemicals, Inc. under the trade name modified methylaluminoxane 3A type) covered by U.S. Patent No. US 5,041,584.

[0102] When the activator is an aluminoxane (modified or unmodified), some embodiments select a maximum activator amount typically at up to 5000-fold molar excess (Al / M) relative to the catalyst compound (per metal catalytic site). The minimum activator to catalyst compound ratio is a 1:1 molar ratio. Alternative preferred ranges include 1:1-500:1, or 1:1-200:1, or 1:1-100:1, or 1:1-50:1.

[0103] In one class of embodiments, little or no alumoxane is used in the polymerization process described herein. Preferably, the alumoxane is present at 0 mol%, or the alumoxane is present at a molar ratio of aluminum to catalyst compound transition metal of less than 500:1, preferably less than 300:1, preferably less than 100:1, preferably less than 1:1.

[0104] In another class of embodiments, at least one activator comprises aluminum and the ratio of aluminum to transition metal, e.g., hafnium or zirconium, is at least 150: 1; at least one activator comprises aluminum and the ratio of aluminum to transition metal, e.g., hafnium or zirconium, is at least 250: 1; or at least one activator comprises aluminum and the ratio of aluminum to transition metal, e.g., hafnium or zirconium, is at least 1,000: 1.

[0105] Ionizing / Non-coordinating Anion Activators

[0106] The term "non-coordinating anion" (NCA) refers to an anion that is not coordinated to the cation or is only weakly coordinated to the cation, thereby remaining sufficiently unstable to be replaced by a neutral Lewis base. "Compatible" non-coordinating anions are those that do not degrade to neutrality when the initially formed complex decomposes. In addition, the anion does not transfer anionic substituents or fragments to the cation, causing it to form a neutral transition metal compound and neutral by-products from the anion. Non-coordinating anions that can be used according to the present invention are such anions that are compatible, stabilizing the transition metal cation at +1 in the sense of balancing its ionic charge, yet remaining sufficiently unstable to allow displacement during the polymerization process. Ionizing activators useful herein typically comprise NCAs, especially compatible NCAs.

[0107] It is within the scope of the present invention to use a neutral or ionic ionizing activator, such as tri(n-butyl)ammonium tetrakis(pentafluorophenyl)borate, a triperfluorophenylborane metalloid precursor or a triperfluoronaphthylborane metalloid precursor, a polyhalogenated heteroborane anion (WO 98 / 43983), boric acid (US 5,942,459) or a combination thereof. It is also within the scope of the present invention to use a neutral or ionic activator alone or in combination with an aluminoxane or modified aluminoxane activator.

[0108] See US 8,658,556 and US 6,211,105 for descriptions of useful activators.

[0109] Preferred activators include N,N-dimethylanilinium tetrakis(perfluoronaphthyl)borate, N,N-dimethylanilinium tetrakis(perfluorobiphenyl)borate, N,N-dimethylanilinium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, N,N-dimethylanilinium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, triphenylcarbon tetrakis(perfluoronaphthyl)borate, Tetrakis(perfluorobiphenyl) borate triphenylcarbon triphenylcarbon tetrakis(3,5-bis(trifluoromethyl)phenyl)borate Triphenylcarbon tetrakis(perfluorophenyl)borate [Me3NH + ][B(C6F5)4 - ]; 1-(4-(tris(pentafluorophenyl)boronic acid)-2,3,5,6-tetrafluorophenyl)pyrrolidine salt; and tetrakis(pentafluorophenyl)borate, 4-(tris(pentafluorophenyl)boronic acid)-2,3,5,6-tetrafluoropyridine.

[0110] In a preferred embodiment, the activator comprises a triarylcarbonyl (e.g. triphenylcarbon tetraphenylborate Triphenylcarbon tetrakis(pentafluorophenyl)borate Triphenylcarbon tetrakis(2,3,4,6-tetrafluorophenyl)borate Triphenylcarbon tetrakis(perfluoronaphthyl)borate Tetrakis(perfluorobiphenyl) borate triphenylcarbon triphenylcarbon tetrakis(3,5-bis(trifluoromethyl)phenyl)borate ).

[0111] In another embodiment, the activator comprises one or more of the following: trialkylammonium tetrakis(pentafluorophenyl)borate, N,N-dialkylanilinium tetrakis(pentafluorophenyl)borate, N,N-dimethyl-(2,4,6-trimethylanilinium tetrakis(pentafluorophenyl)borate, trialkylammonium tetrakis(2,3,4,6-tetrafluorophenyl)borate, N,N-dialkylanilinium tetrakis(2,3,4,6-tetrafluorophenyl)borate, trialkylammonium tetrakis(perfluoronaphthyl)borate, N,N-dialkylanilinium tetrakis(perfluoronaphthyl)borate , trialkylammonium tetrakis(perfluorobiphenyl)borate, N,N-dialkylanilinium tetrakis(perfluorobiphenyl)borate, trialkylammonium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, N,N-dialkylanilinium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, N,N-dialkyl-(2,4,6-trimethylanilinium tetrakis(3,5-bis(trifluoromethyl)phenyl)borate, di(isopropyl)ammonium tetrakis(pentafluorophenyl)borate, (wherein the alkyl group is methyl, ethyl, propyl, n-butyl, sec-butyl or tert-butyl).

[0112] Typical activator to catalyst ratios, such as all NCA activators to catalyst ratios, are about 1: 1 molar ratios. Alternative preferred ranges include 0.1: 1-100: 1, or 0.5: 1-200: 1, or 1: 1-500: 1, or 1: 1-1000: 1. Particularly useful ranges are 0.5: 1-10: 1, preferably 1: 1-5: 1.

[0113] Carrier material

[0114] The catalyst composition may optionally include at least one "carrier" or sometimes also referred to as a "support". The terms may be interchangeable unless otherwise distinguished. Suitable carriers include, but are not limited to, silica, alumina, silica-alumina, zirconium oxide, titanium oxide, silica-alumina, cerium oxide, magnesium oxide, or a combination thereof. The catalyst may optionally include a carrier or be arranged on at least one carrier. Suitable carriers include, but are not limited to, active and inactive materials, synthetic or naturally occurring zeolites, and inorganic materials such as clays and / or oxides such as silica, alumina, zirconium oxide, titanium oxide, silica-alumina, cerium oxide, magnesium oxide, or a combination thereof. In particular, the carrier may be silica-alumina, aluminum oxide, and / or a zeolite, especially aluminum oxide. Silica-alumina may be naturally occurring or in the form of a gelatinous precipitate or gel comprising a mixture of silica and a metal oxide.

[0115] In one class of embodiments, at least one carrier may comprise an organosilica material. The organosilica material carrier may be a polymer formed from at least one monomer. In certain embodiments, the organosilica material may be a polymer formed from a plurality of different monomers. Methods and materials for preparing organosilica materials and characterization descriptions may be found in, for example, WO 2016 / 094770 and WO 2016 / 094774.

[0116] Scavengers, chain transfer agents and / or co-activators

[0117] Scavengers, chain transfer agents or co-activators may also be used. Alkyl aluminum compounds that may be used as scavengers or co-activators include, for example, one or more of those represented by the formula AlR3, wherein each R is independently a C1-C8 aliphatic group, preferably methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl or isomers thereof), particularly trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, tri-n-hexyl aluminum, tri-n-octylaluminum or mixtures thereof.

[0118] Useful chain transfer agents that may also be used herein are typically those of the formula AlR 20 3. ZnR 20 2 represented by a compound (wherein each R 20 The alkyl group is independently a C1-C8 aliphatic group, preferably a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, an octyl group or an isomer thereof) or a combination thereof, for example, diethylzinc, trimethylaluminum, triisobutylaluminum, trioctylaluminum or a combination thereof.

[0119] Aggregation methods

[0120] In embodiments herein, the invention relates to a polymerization process wherein monomers (e.g., propylene and / or ethylene), and optionally, comonomers, are contacted with a catalyst system comprising at least one activator, at least one support, and at least one catalyst, such as a metallocene compound, as described above. The support, catalyst compound, and activator may be combined in any order, and are typically combined prior to contact with the monomers.

[0121] Monomers useful herein include substituted or unsubstituted C2-C 40 α-olefins, preferably C2-C 20 α-olefins, preferably C2-C 12 The α-olefins are preferably ethylene, propylene, butene, pentene, hexene, heptene, octene, nonene, decene, undecene, dodecene and isomers thereof.

[0122] In one embodiment of the invention, the monomers include propylene and optionally comonomers, wherein the comonomers include one or more ethylene or C4-C 40 Olefins, preferably C4-C 20 Olefins, or preferably C6-C 12 Olefins. C4-C 40 The olefin monomers may be linear, branched or cyclic. 40 The cyclic olefins may be strained or unstrained, monocyclic or polycyclic, and may optionally include heteroatoms and / or one or more functional groups.

[0123] In another embodiment of the present invention, the monomers include ethylene and optionally comonomers, wherein the comonomers include one or more C3-C 40 Olefins, preferably C4-C 20 Olefins, or preferably C6-C 12 Olefins. 40 The olefin monomers may be linear, branched or cyclic. 40 The cyclic olefins may be strained or unstrained, monocyclic or polycyclic, and may optionally include heteroatoms and / or one or more functional groups.

[0124] Exemplary C2-C 40Examples of olefin monomers and optional comonomers include ethylene, propylene, butene, pentene, hexene, heptene, octene, nonene, decene, undecene, dodecene, norbornene, norbornadiene, dicyclopentadiene, cyclopentene, cycloheptene, cyclooctene, cyclooctadiene, cyclododecene, 7-oxanorbornene, 7-oxanorbornadiene, substituted derivatives thereof and isomers thereof, preferably hexene, heptene, octene, nonene, decene, dodecene, cyclooctene, 1,5-cyclooctadiene, 1-hydroxy-4-cyclooctene, 1-acetoxy-4-cyclooctene, 5-methylcyclopentene, cyclopentene, dicyclopentadiene, norbornene, norbornadiene and their corresponding homologs and derivatives, preferably norbornene, norbornadiene and dicyclopentadiene.

[0125] In a preferred embodiment, one or more dienes are present in the polymers prepared herein in an amount of up to 10 wt %, preferably in an amount of 0.00001 to 1.0 wt %, preferably 0.002 to 0.5 wt %, even more preferably 0.003 to 0.2 wt %, based on the total weight of the composition. In some embodiments, 500 ppm or less of diene, preferably 400 ppm or less, preferably 300 ppm or less of diene are added to the polymerization. In other embodiments, at least 50 ppm of diene, or 100 ppm or more, or 150 ppm or more are added to the polymerization.

[0126] The diene monomers useful in the present invention include any hydrocarbon structure having at least two unsaturated bonds, preferably C4-C 30, wherein at least two of the unsaturated bonds are easily introduced into the polymer by stereospecific or non-stereospecific catalysts (one or more). It is further preferred that the diene monomer is selected from α, ω-diene monomers (i.e., divinyl monomers). More preferably, the diene monomer is a linear divinyl monomer, very preferably, those containing 4-30 carbon atoms. Examples of preferred dienes include butadiene, pentadiene, hexadiene, heptadiene, octadiene, nonadiene, decadiene, undecadiene, dodecadiene, tridecadiene, tetradecadiene, pentadecadiene, hexadecadiene, heptadecadiene, octadecadiene, nonadecadiene, eicosadiene, heneicosadiene, docosadiene, tricosadiene, tetracosadiene, pentacosadiene, hexacosadiene, heptacosadiene, octacosadiene, nonacosadiene, triacontadiene, and particularly preferred dienes include 1,6-heptadiene, 1,7-octadiene, 1,8-nonadiene, 1,9-decadiene, 1,10-undecadiene, 1,11-dodecadiene, 1,12-tridecadiene, 1,13-tetradecadiene, and low molecular weight polybutadiene (Mw less than 1000 g / mol). Preferred cyclic dienes include cyclopentadiene, vinyl norbornene, norbornadiene, ethylidene norbornene, divinylbenzene, dicyclopentadiene or higher ring containing dienes with or without substituents at various ring positions.

[0127] The polymerization process according to the disclosure of the present application can be carried out in any manner known in the art. Any suspension, slurry, high pressure tubular or autoclave process or gas phase polymerization process known in the art can be used under polymerizable conditions. These methods can be operated in intermittent, semi-intermittent or continuous modes. Heterogeneous polymerization processes (e.g., gas phase and slurry phase processes) are useful. Multiphase processes are defined as processes in which the catalyst system is insoluble in the reaction medium. Alternatively, in other embodiments, the polymerization process is heterogeneous.

[0128] A homogeneous polymerization process is defined as a process in which at least 90 wt% of the preferred product is soluble in the reaction medium. Alternatively, it is particularly preferred that the polymerization process is not a bulk process. In one class of embodiments, a bulk process is defined as a process in which the monomer concentration in all feeds to the reactor is preferably 70 vol% or higher. Alternatively, neither solvent nor diluent is present in or added to the reaction medium (except for a small amount used as a support for the catalyst system or other additives, or an amount that is typically coexistent with the monomer, such as propane in propylene). In another embodiment, the process is a slurry process. The term "slurry polymerization process" as used herein refers to a polymerization process in which a supported catalyst is used and the monomers are polymerized on the supported catalyst particles. At least 95 wt% of the polymer product derived from the supported catalyst is in granular form as solid particles (not dissolved in the diluent).

[0129] Suitable diluents / solvents for the polymerization include non-coordinating inert liquids. Examples include straight chain and branched hydrocarbons such as isobutane, butane, pentane, isopentane, hexane, isohexane, heptane, octane, dodecane and mixtures thereof; cyclic and alicyclic hydrocarbons such as cyclohexane, cycloheptane, methylcyclohexane, methylcycloheptane and mixtures thereof such as those available commercially (Isopar TM ); perhalogenated hydrocarbons such as perfluorinated C 4-10 Alkanes, chlorobenzenes and aromatic and alkyl substituted aromatic compounds such as benzene, toluene, mesitylene and xylene. Suitable solvents also include liquid olefins that can act as monomers or comonomers, including ethylene, propylene, 1-butene, 1-hexene, 1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 1-octene, 1-decene and mixtures thereof. In a preferred embodiment, aliphatic hydrocarbon solvents are used as solvents, such as isobutane, butane, pentane, isopentane, hexane, isohexane, heptane, octane, dodecane and mixtures thereof; cyclic and alicyclic hydrocarbons, such as cyclohexane, cycloheptane, methylcyclohexane, methylcycloheptane and mixtures thereof. In another embodiment, the solvent is a non-aromatic solvent, preferably aromatic compounds are present in the solvent in an amount of less than 1 wt%, preferably less than 0.5 wt%, preferably less than 0 wt%, based on the weight of the solvent.

[0130] In a preferred embodiment, the feed concentration of monomers and comonomers for the polymerization is 60 vol% solvent or less, preferably 40 vol% or less, preferably 20 vol% or less, based on the total volume of the feed stream. Preferably, the polymerization is run as a bulk process.

[0131] Preferred polymerizations can be run at any temperature and / or pressure suitable for obtaining the desired ethylene polymer and as described above. In some embodiments, typical pressures include pressures of about 0.35 MPa to about 10 MPa, preferably about 0.45 MPa to about 6 MPa, or preferably about 0.5 MPa to about 4 MPa.

[0132] In some embodiments, hydrogen is present in the polymerization reactor at a partial pressure of 0.001-50 psig (0.007-345 kPa), preferably 0.01-25 psig (0.07-172 kPa), and more preferably 0.1-10 psig (0.7-70 kPa).

[0133] In one class of embodiments, polymerization is carried out in the gas phase, preferably, in a fluidized bed gas phase process. Generally speaking, in a fluidized bed gas phase process for preparing polymers, a gaseous stream comprising one or more monomers is continuously circulated through a fluidized bed in the presence of a catalyst under reactive conditions. The gaseous stream is discharged from the fluidized bed and recycled back to the reactor. Simultaneously, polymer product is discharged from the reactor and fresh monomer is added to replace the polymerized monomer. See, for example, U.S. Patent Nos. 4,543,399; 4,588,790; 5,028,670; 5,317,036; 5,352,749; 5,405,922; 5,436,304; 5,453,471; 5,462,999; 5,616,661; and 5,668,228; all of which are incorporated herein by reference in their entirety.

[0134] In another embodiment of the present invention, polymerization is carried out in a slurry phase. Slurry polymerization processes are generally operated in the range of 1 to about 50 atmospheres (15psi-735psi, 103kPa-5068kPa) or even greater and at the above-mentioned temperatures. In slurry polymerization, a suspension of solid, granular polymer is formed in a liquid phase polymerization diluent medium to which monomers and comonomers are added together with a catalyst. The suspension including the diluent is intermittently or continuously removed from a reactor, in which the volatile components are separated from the polymer and circulated (optionally, after distillation) to the reactor. The liquid diluent used for the polymerization medium is typically an alkane containing 3-7 carbon atoms, preferably a branched alkane. The medium used should be liquid and relatively inert under polymerization conditions. When a propane medium is used, the method is typically operated above the reaction diluent critical temperature and pressure. Typically, a hexane or isobutane medium is used.

[0135] In one embodiment, the preferred polymerization technique that can be used in the present invention is called particle formation polymerization, or slurry process, in which the temperature is maintained at less than the temperature at which the polymer enters the solution. Such techniques are well known in the art and are described, for example, in U.S. Patent No. 3,248,179. The preferred temperature in the particle formation process is in the range of about 85°C to about 110°C. Two preferred polymerization methods of the slurry process are those using a loop reactor and those using multiple stirred reactors in series, in parallel or in combination thereof. Non-limiting examples of slurry processes include continuous loop or stirred tank processes. In addition, other examples of slurry processes are described in U.S. Patent No. 4,613,484, which is incorporated herein by reference in its entirety.

[0136] In another embodiment, the slurry process is carried out continuously in a loop reactor. The catalyst (either as a slurry in isobutane or as a dry free-flowing powder) is periodically injected into the reactor loop, which is itself filled with a circulating slurry of growing polymer particles in a diluent of isobutane containing monomer and comonomer. Optionally, hydrogen can be added as a molecular weight control. In one embodiment, 500 ppm or less of hydrogen is added, or 400 ppm or less or 300 ppm or less. In other embodiments, at least 50 ppm of hydrogen is added, or 100 ppm or more, or 150 ppm or more.

[0137] The heat of reaction is removed via the loop tube wall, as the bulk of the reactor is in the form of a double-jacketed tube. The slurry is allowed to exit the reactor periodically or continuously, in sequence to a hot low-pressure flash vessel, a rotary dryer, and a nitrogen purge column to remove the isobutane diluent and all unreacted monomers and comonomers. The resulting hydrocarbon-free powder is then compounded for use in a variety of applications.

[0138] In a preferred embodiment, the catalyst system used in the polymerization comprises at most one catalyst compound. A "reaction zone" also referred to as a "polymerization zone" is a container, such as a batch reactor, in which polymerization is carried out. When multiple reactors are used in a series or parallel configuration, each reactor is considered to be a separate polymerization zone. For multi-stage polymerization in both batch reactors and continuous reactors, each polymerization stage is considered to be a separate polymerization zone. In a preferred embodiment, polymerization occurs in one reaction zone.

[0139] Useful reactor types and / or processes for preparing polyolefin polymers include, but are not limited to, UNIPOL TM Gas phase reactor (available from Univation Technologies); INEOS TM Gas phase reactors and processes; Continuous flow stirred tank (CSTR) reactors (solution and slurry); Plug flow tubular reactors (solution and slurry); Slurry: (e.g., slurry loops (single or dual loops)) (available from Chevron Phillips Chemical Company) and (tandem reactors) (available from Mitsui Chemicals)); BORSTAR TM Process and reactor (slurry combined with gas); and multi-zone circulation reactor (MZCR), such as the SPHERIZONE available from LyondellBasell TM Reactors and methods.

[0140] In several classes of embodiments, the catalyst activity for the polymerization reaction is at least 4,250 g / g*catalyst or greater, at least 4,750 g / g*catalyst or greater, at least 5,000 g / g*catalyst or greater, at least 6,250 g / g*catalyst or greater, at least 8,500 g / g*catalyst or greater, at least 9,000 g / g*catalyst or greater, at least 9,500 g / g*catalyst or greater, or at least 9,700 g / g*catalyst or greater.

[0141] product

[0142] In one embodiment, the method described herein prepares a metallocene-catalyzed polyethylene, wherein the composition comprises one, two, three, four or more C2-C 40 Olefin monomers, e.g., C2-C 20 Homopolymers and copolymers of α-olefin monomers.

[0143] For example, metallocene-catalyzed polyethylenes include C2-C 40 Olefins and one, two or three or more different C2-C 40 The copolymer of olefins (wherein the C2-C 40 The olefin is preferably C3-C 20 Olefins, preferably C3-C 12 α-olefins, preferably propylene, butene, hexene, octene, decene, dodecene, preferably propylene, butene, hexene, octene or mixtures thereof).

[0144] The metallocene-catalyzed polyethylene may comprise at least 65 wt%, 99.0 to about 80.0 wt%, 99.0 to 85.0 wt%, 99.0 to 87.5 wt%, 99.0 to 90.0 wt%, 99.0 to 92.5 wt%, 99.0 to 95.0 wt%, or 99.0 to 97.0 wt% of polymer units derived from ethylene and 0.5 to 20 wt%, about 1.0 to about 20.0 wt%, 1.0 to 15.0 wt%, 0.5 to 12.5 wt%, 1.0 to 10.0 wt%, 1.0 to 7.5 wt%, 1.0 to 5.0 wt%, or 1.0 to 3.0 wt% of polymer units derived from one or more C3-C 20 α-olefin comonomer, preferably C3-C 12 α-olefins, preferably C3-C 10 Polymer units of α-olefins, more preferably C4-C8 α-olefins, such as hexene and octene. The α-olefin comonomer may be linear or branched, and two or more comonomers may be used if desired.

[0145] Examples of suitable comonomers include propylene, butene, 1-pentene; 1-pentene containing one or more methyl, ethyl or propyl substituents; 1-hexene; 1-hexene containing one or more methyl, ethyl or propyl substituents; 1-heptene; 1-heptene containing one or more methyl, ethyl or propyl substituents; 1-octene; 1-octene containing one or more methyl, ethyl or propyl substituents; 1-nonene; 1-nonene containing one or more methyl, ethyl or propyl substituents; 1-decene substituted with ethyl, methyl or dimethyl; 1-dodecene and styrene. Particularly suitable comonomers include 1-butene, 1-hexene and 1-octene, 1-hexene and mixtures thereof.

[0146] The metallocene-catalyzed polyethylene can have a melt index (MI) of ≥ about 0.10 g / 10 min, 0.1 g / 10 min to 30 g / 10 min, 0.1 g / 10 min to 6 g / 10 min, or, for example, ≥ about 0.15 g / 10 min, ≥ about 0.18 g / 10 min, ≥ about 0.20 g / 10 min, ≥ about 0.22 g / 10 min, ≥ about 0.25 g / 10 min, ≥ about 0.28 g / 10 min, or ≥ about 0.30 g / 10 min according to the following test method: 2.16 and further a melt index (I) of ≤ about 3.00 g / 10 min, e.g., ≤ about 2.00 g / 10 min, ≤ about 1.00 g / 10 min, ≤ about 0.70 g / 10 min, ≤ about 0.50 g / 10 min, ≤ about 0.40 g / 10 min or ≤ about 0.30 g / 10 min. 2.16 ). Specifically disclosed ranges include, but are not limited to, ranges formed by combinations of any of the above-recited values, such as about 0.10 to about 0.30, about 0.15 to about 0.25, about 0.18 to about 0.22 g / 10 min, etc.

[0147] The metallocene-catalyzed polyethylene may have a high load melt index (HLMI) of 1 to 60 g / 10 min, 5 to 40 g / 10 min, 15 to 40 g / 10 min, or 18 to 39.5 g / 10 min according to the following test method: 21.6 ).

[0148] The metallocene-catalyzed polyethylene may have a melt index ratio (MIR) of 10-90, 20-45, 25-60, alternatively, 30-55, alternatively, 35-50, alternatively 40-46. MIR is defined as 21.6 / I 2.16 .

[0149] Metallocene-catalyzed polyethylene can have a density of 0.900 g / cm3 -0.930g / cm 3 or having a density of approximately 0.890 g / cm 3 , about 0.918g / cm 3 , ≥ about 0.920g / cm 3 , for example, ≥ about 0.922 g / cm 3 , ≥ about 0.928g / cm 3 , ≥ about 0.930g / cm 3 , ≥ about 0.932g / cm 3 In addition, the metallocene-catalyzed polyethylene may have a density of ≤ about 0.945 g / cm 3 , for example ≤ about 0.940 g / cm 3 , ≤ about 0.937g / cm 3 , ≤ about 0.935g / cm 3 , ≤ about 0.933g / cm 3 or ≤ about 0.930g / cm 3 Density. Specifically disclosed ranges include, but are not limited to, ranges formed by any combination of the values ​​listed above, for example, about 0.920-about 0.945 g / cm 3 , 0.920-0.930g / cm 3 , 0.925-0.935g / cm 3 , 0.920-0.940g / cm 3 etc. The density is determined according to the following test method.

[0150] The metallocene-catalyzed polyethylene may have a molecular weight distribution (MWD, defined as Mw / Mn) of about 2 to about 12, about 5 to about 10.5 or 11, about 2.5 to about 5.5, preferably 4.0 to 5.0 and about 4.4 to 5.0.

[0151] In one class of embodiments, the metallocene-catalyzed polyethylene comprises at least 65 wt% ethylene-derived units and 0-35 wt% C3-C 12 Olefin comonomer-derived units, based on the total weight of the metallocene-catalyzed polyethylene; wherein the metallocene-catalyzed polyethylene has:

[0152] a) 100 kg / mol or greater, alternatively, 110 kg / mol or greater, alternatively, 125 kg / mol or greater, alternatively, 150 kg / mol or greater, alternatively, 170 kg / mol or greater, alternatively, RCI,m of 185 kg / mol or greater; wherein RCI,m represents reversed-co-monomer index (RCI,m), for its definition and test method, refer to the disclosure of the prior document US20190119417A1.

[0153] and one or both of the following:

[0154] b) Tw of -16 to -38°C 1- a Tw2 value, alternatively, a Tw1-Tw2 value of -23 to -36°C, alternatively, a Tw1-Tw2 value of -23 to -33°C; and

[0155] c) a Mw1 / Mw2 value of at least 0.9, alternatively, a Mw1 / Mw2 value of 0.9-4, alternatively, a Mw1 / Mw2 value of 1.25-4;

[0156] and one or more of the following:

[0157] d)0.890g / cm 3 -0.940g / cm 3 density;

[0158] e) a melt index (MI) of 0.1 g / 10 min to 30 g / 10 min, alternatively, a melt index (MI) of 0.1 g / 10 min to 6 g / 10 min;

[0159] f) Melt index ratio (I) 10-90 21 / I2);

[0160] g) Mw / Mn of 2 to 12;

[0161] h) Mz / Mw of 2.5-5.0;

[0162] i) Mz / Mn of 10-40; and

[0163] j) 0.900 or more, alternatively, 0.930 or more, alternatively, 0.940 or more, alternatively 0.994 or more g' (vis) .

[0164] The measurement of the parameters described in this application can be specifically referred to the disclosure of US20190119417A1, in particular Tw1, Tw2, Mw1 and Mw2 are measured by CFC. In any embodiment described herein, the metallocene-catalyzed polyethylene can be a multimodal metallocene-catalyzed polyethylene such as a bimodal metallocene-catalyzed polyethylene. "Multimodal" as used herein refers to the presence of at least two distinguishable peaks in the molecular weight distribution curve of the metallocene-catalyzed polyethylene (determined using gel permeation chromatography (GPC) or other recognized analytical techniques). For example, if there are two distinguishable peaks in the molecular weight distribution curve, such a composition can be referred to as a bimodal composition. Typically, if there is only one peak (e.g., a single peak), there is no obvious valley between the peaks, any of the peaks is not considered a distinguishable peak, or the two peaks are not considered distinguishable peaks, then such a composition can be referred to as a non-bimodal composition. For example, in U.S. Patent Nos. 8,846,841 and 8,691,715, Figure 1-5 Representative bimodal molecular weight distribution curves are shown. In these figures, there are valleys between peaks, and the peaks can be independent or deconvoluted. Typically, a bimodal molecular weight distribution is characterized as having an identifiable high molecular weight component (or distribution) and an identifiable low molecular weight component (or distribution). In contrast, in U.S. Pat. Nos. 8,846,841 and 8,691,715, Figure 6-1 Representative non-bimodal molecular weight distribution curves are shown in 1. These include unimodal molecular weight distributions as well as distribution curves containing two peaks that cannot be easily distinguished, separated or deconvoluted.

[0165] In any of the embodiments described herein, the metallocene-catalyzed polyethylene may have greater than 0.2 total internal unsaturations / 1000 carbon atoms, alternatively, greater than 0.3 total internal unsaturations / 1000 carbon atoms, alternatively, greater than 0.32 total internal unsaturations / 1000 carbon atoms, alternatively, greater than 0.38 total internal unsaturations / 1000 carbon atoms, alternatively, greater than 0.4 total internal unsaturations / 1000 carbon atoms. 1 Internal unsaturation measured by H NMR (see Test Methods below).

[0166] Blends

[0167] As used herein, "blend" may refer to dry or extruder blends of two or more different polymers, and in-reactor blends, including blends produced in a single reactor zone using multiple or mixed catalyst systems, and blends produced in one or more reactors using one or more catalysts under the same or different conditions (e.g., blends produced in a series of reactors (same or different) where each reactor is operated under different conditions and / or with a different catalyst). The blend may also contain at least one additive ingredient (C) to (M): (C) lubricant; (D) polymer processing aid; (E) antioxidant; (F) metal deactivator; (G) UV-accelerated degradation inhibitor as UV stabilizer; (H) slip agent; (I) hindered amine stabilizer; (J) anti-blocking agent; (K) colorant; (L) anti-fog agent; and (M) antistatic agent; provided that the total amount of the at least one additive is >0 to 5 wt% of the polyolefin composition.

[0168] In a preferred embodiment of the present application, the polyethylene blend comprises 50 wt% to 75 wt% of a metallocene-catalyzed polyethylene and 50 wt% to 25 wt% of a linear low-density polyethylene catalyzed by a Ziegler-Natta catalyst, based on the total weight of the polyethylene blend, wherein the metallocene-catalyzed polyethylene has a melt index (MI) of 0.1-6 g / 10 min, preferably 2 g / 10 min, a density of 0.900-0.930 g / cm 3 , preferably 0.925 g / cm 3 , a molecular weight distribution (MWD) of 5-10.5, preferably 5.35, and a composition distribution width index of 10 to 50, preferably 39.53, wherein the linear low density polyethylene catalyzed by the Ziegler-Natta catalyst has a melt index (MI) of 0.5-2.5 g / 10 min, preferably 2 g / 10 min and a density of 0.905-0.930 g / cm 3 , preferably 0.918 g / cm 3 .

[0169] End Use

[0170] Any of the above polymers and compositions in combination with optional additives (see, e.g., U.S. Patent Application Publication No. 2016 / 0060430, paragraphs

[0082] -

[0093] ) can be used in a variety of end-use applications. These end uses can be prepared by methods known in the art. End uses include polymer products and products having specific end uses. Exemplary end uses may include, but are not limited to, films, film-based products, diaper backsheets, industrial filter fabrics, wire and cable coating compositions, articles formed by molding techniques such as injection molding or blow molding, extrusion coating, foaming, casting, and combinations thereof. End uses also include products made from films, e.g., bags, packaging, and personal care films, packets, medical products such as medical films and intravenous (IV) bags.

[0171] membrane

[0172] Films include monolayer or multilayer films. Films include those film structures and film applications known to those skilled in the art. Specific end-use films include, for example, blown films, cast films, stretch films, stretch / cast films, stretch cling films, stretch hand roll films, mechanical stretch wraps, shrink films, shrink wrap films, greenhouse films, laminates and laminated films. Exemplary films can be prepared by any conventional method known to those skilled in the art, such as by techniques for preparing blown, extruded and / or cast stretch and / or shrink films (including shrink-on-shrink applications).

[0173] In one embodiment, the multilayer film or multi-layer film can be formed by methods known in the art. The total thickness of the multilayer film can be changed based on the desired application. About 5-100 μm, more generally about 10-50 μm of the total film thickness is suitable for most applications. Those skilled in the art will appreciate that the thickness of each layer of the multilayer film can be adjusted according to the desired end-use performance, the resin or copolymer used, the equipment production capacity and other factors. The material forming each layer can be co-extruded through the co-extrusion feed section and the die assembly to produce a film with two or more layers that adhere together but have different compositions. Coextrusion can be suitable for use in cast film or blown film methods simultaneously. Exemplary multilayer films have at least two, at least three or at least four layers. In one embodiment, the multilayer film is composed of five to ten layers.

[0174] To facilitate discussion of different film structures, the following notation is used herein. Each layer of the film is represented as "A" or "B". When the cast film includes more than one A layer or more than one B layer, one or more prime symbols (', ", ", ", etc.) are appended to the A or B symbol to represent the same type of layers, which may be the same or may be different in one or more properties such as chemical composition, density, melt index, thickness, etc. Finally, the symbols of adjacent layers are separated by a slash ( / ). Using this notation, a three-layer film having an inner layer arranged between two outer layers would be represented as A / B / A'. Similarly, a five-layer film of alternating layers would be represented as A / B / A' / B' / A". Unless otherwise noted, for the purposes described herein, the left-to-right or right-to-left order of the layers is not significant, nor is the order of the prime symbols; for example, an A / B film is equivalent to a B / A film, and an A / A' / B / A'' film is equivalent to an A / B / A' / A" film. The relative thickness of each film layer is expressed similarly, where the thickness of each layer relative to the total film thickness of 100 (dimensionless) is expressed numerically and separated by slashes, for example, the relative thickness of an A / B / A' film having A and A' layers (each 10 μm) and a 30 μm B layer is expressed as 20 / 60 / 20.

[0175] The thickness of each layer of the film, and the entire film is not particularly limited, but is determined according to the desired properties of the film. Typical film layers have a thickness of about 1 to about 1000 μm, more usually about 5 to about 100 μm, and typical films have a total thickness of about 10 to about 100 μm.

[0176] In some embodiments, and using the above nomenclature, the present invention provides multilayer films having any of the following exemplary structures: (a) bilayer films, such as A / B and B / B'; (b) trilayer films, such as A / B / A', A / A' / B, B / A / B', and B / B' / B"; (c) quadlayer films, such as A / A' / A" / B, A / A' / B / A", A / A' / B / B', A / B / A' / B', A / B / B' / A', B / A / A' / B', A / B / B' / B", B / A / B' / B", and B / B' / B" / B'"; (d) pentalayer films, such as A / A' / A" / A'" / B, A / A' / A" / B / A'", A / A' / B / A" / A'", A / A' / A" / B / B' , A / A' / B / A" / B', A / A' / B / B' / A", A / B / A' / B' / A", A / B / A' / A" / B, B / A / A' / A" / B' ,A / A' / B / B' / B",A / B / A' / B' / B",A / B / B' / B" / A',B / A / A' / B' / B",B / A / B' / A' / B" , B / A / B' / B" / A', A / B / B' / B" / B'", B / A / B' / B" / B'", B / B' / A / B" / B'" and B / B' / B" / B'" / B""; and similar structures having films with 6, 7, 8, 9, 24, 48, 64, 100 or any other number of layers. It goes without saying that films having still more layers can be used.

[0177] In any of the above embodiments, one or more A layers can be replaced with a substrate layer, such as glass, plastic, paper, metal, etc., or the entire film can be coated or laminated to a substrate. Therefore, although the discussion here focuses on multilayer films, the films can also be used as coatings for substrates such as paper, metal, glass, plastic, and other materials that can receive coatings.

[0178] The film may be further embossed, or produced, or processed according to other known film processes. The film may be tailored to a specific application by adjusting the thickness, material and sequence of the various layers as well as additives in each layer or modifiers applied to each layer.

[0179] Stretch Film

[0180] The above polymers and compositions can be used to prepare stretch films. Stretch films are widely used in various bundling and packaging applications. The term "stretch film" refers to a film that can be stretched and exert a bundling force and includes films that are stretched at the time of application as well as "pre-stretched" films, i.e., films that are provided in a pre-stretched form for use without additional stretching. Stretch films can be monolayer films or multilayer films and can include conventional additives, such as adhesion enhancing additives such as tackifiers, and non-adhesive or slip additives to customize the slip / adhesion properties of the film.

[0181] Shrink Film

[0182] The above polymers and compositions can be used to prepare shrink films. Shrink films (also referred to as heat shrinkable films) are widely used in industrial and retail bundling and packaging applications. Such films can shrink when heat is applied to release stresses imparted to the film during or after extrusion. Shrinkage can occur in one direction or in both the longitudinal and transverse directions. Conventional shrink films are described, for example, in WO 2004 / 022646.

[0183] Industrial shrink films are commonly used to bundle products on pallets. Typical industrial shrink films are formed in a single bubble blown extrusion process to a thickness of about 80-200 μm and provide shrinkage in both directions, typically at a machine direction (MD) to transverse direction (TD) ratio of about 60:40. Retail films are commonly used to package and / or bundle products for consumer use, such as for supermarket merchandise. Such films are typically formed in a single bubble blown extrusion process to a thickness of about 35-80 μm, with a typical MD:TD shrink ratio of about 80:20.

[0184] The films may be used for "shrink-on-shrink" applications. As used herein, "shrink-on-shrink" refers to a method in which an outer shrink wrap layer is applied around one or more items that have already been individually shrink wrapped (here, the "inner layer" of the wrap). In these methods, it is desirable that the film used to wrap the individual items has a higher melting (or shrink) point than the film used for the outer layer. When such a configuration is used, the desired level of shrinkage can be achieved in the outer layer while preventing the inner layer from melting, further shrinking, or otherwise distorting during the shrinkage of the outer layer. Some of the films described herein have been observed to have sharp shrink points when subjected to heat from a heat gun at high heat setting, indicating that they may be particularly suitable for use as an inner layer in various shrink-on-shrink applications.

[0185] Greenhouse film

[0186] Polymers and compositions as described above can be used to prepare stretching to prepare greenhouse films. Greenhouse films are generally thermal insulation films that require different heat retention depending on the climate. Films that are less thermally insulating are used in warmer regions or for spring applications. Films that are more thermally insulating are used in winter months and for colder regions.

[0187] bag

[0188] Bags include those bag structures and bag applications known to those skilled in the art. Exemplary bags include shipping bags, grocery bags and dunnage, industrial dunnage, produce bags, and heavy duty bags.

[0189] Package

[0190] Packages include those packaging structures and packaging applications known to those skilled in the art. Exemplary packages include flexible packaging, food packaging, such as fresh-cut produce packaging, frozen food packaging, bundling, packaging and unitizing various products. Applications of such packaging include various foods, carpet rolls, liquid containers and various similar commodities that are containerized and / or placed on pallets for shipping, storage and / or display.

[0191] Blow molding products

[0192] The above polymers and compositions can also be used in blow molding methods and applications. Such methods are well known in the art and include methods of inflating a hot, hollow thermoplastic preform (or parison) inside a closed mold. In this way, the shape of the parison conforms to the shape of the mold cavity, thereby enabling the preparation of a wide variety of hollow parts and containers.

[0193] In a typical blow molding process, a parison is formed between the mold halves and the mold is closed around the parison, sealing one end of the parison and closing the parison around the core mold at the other end. Air is then blown through the core mold (or through a needle) to inflate the parison inside the mold. The mold is then cooled and the part formed inside the mold solidifies. Finally, the mold is opened and the molded part is ejected. The method is applicable to any design with a hollow shape, including but not limited to bottles, cans, toys, daily necessities, automotive parts and other hollow containers and / or parts.

[0194] Blow molding processes may include extrusion and / or injection blow molding. Extrusion blow molding is typically suitable for forming articles having a considerable weight, such as greater than about 12 ounces, including but not limited to food, clothing, or waste containers. Injection blow molding is typically used to obtain precise and uniform wall thickness, high quality neck finish, and to process polymers that cannot be extruded. Typical injection blow molding applications include, but are not limited to, pharmaceuticals, cosmetics, and single-serve containers, typically weighing less than 12 ounces.

[0195] Injection molding products

[0196] The above polymers and compositions can also be used for injection molding applications. Injection molding is a method generally known in the art and is a method that usually occurs in a cyclic manner. The cycle time is generally 10-100 seconds and is controlled by the cooling time of the polymer or polymer blend used. In a typical injection molding cycle, polymer pellets or powders are fed from a hopper and melted in a reciprocating screw type injection molding machine. The screw in the machine rotates forward, filling the mold with the melt and maintaining the melt under high pressure. As the melt cools and shrinks in the mold, the machine adds the melt to the mold to compensate. Once the mold is filled, it is separated from the injection unit and the melt is cooled and solidified. The solidified part is ejected from the mold, and then the mold is closed to prepare the next injection of the melt from the injection unit. The injection molding method provides high productivity, good reproducibility, minimized scrap loss and little to no need for part finishing. Injection molding is suitable for a wide variety of applications, including containers, daily necessities, automotive components, electronic components and many other solid products.

[0197] Extrusion coating

[0198] Above-mentioned polymer and composition can be used for extrusion coating method and application.Extrusion coating is a plastic manufacturing method, wherein molten polymer is extruded and applied to non-plastic carrier or substrate, for example on paper or aluminum to obtain multi-material composite structure.This composite structure typically combines the toughness, sealing and impedance performance of polymer formulation with the barrier, stiffness or aesthetic attributes of non-polymer substrate.In this method, when polymer is extruded from slot die, substrate is typically fed with molten polymer from coil, which is similar to cast film method.The resulting structure is cooled, typically cooled with chill rolls, and wound into finished product rolls.Extrusion coating materials are typically used for food and non-food packaging, pharmaceutical packaging and manufacture for construction (insulating elements) and photographic industry (paper) goods.

[0199] Foam products

[0200] The above polymers and compositions can be used for foaming applications. In the extrusion foaming process, a blowing agent, such as carbon dioxide, nitrogen, or a compound that decomposes to form carbon dioxide or nitrogen, is injected into the polymer melt using a metering unit. The blowing agent is then dissolved in the polymer in an extruder and the pressure is maintained throughout the extruder. A rapid pressure drop rate produces a foamed polymer with a homogeneous pore structure when leaving the extruder. The resulting foamed product is typically lightweight, strong, and is suitable for a wide range of applications in industry such as packaging, automobiles, aerospace, transportation, electrical and electronic instruments, and manufacturing.

[0201] Wire and Cable Applications

[0202] Also provided are electrical articles and devices comprising one or more layers formed from or comprising the above polymers and compositions. Such devices include, for example, electronic instrument cables, computers and computer-related equipment, marine cables, power cables, communication cables or data transmission cables, and hybrid power / communication cables.

[0203] The electrical appliances described herein can be formed by methods known in the art, for example, by one or more extrusion coating steps in a reactor / extruder equipped with a cable die. Such cable extrusion equipment and methods are well known. In a typical extrusion method, an optionally heated conductive core is pulled via a hot extrusion die, typically a right angle die, wherein a layer of a molten polymer composition is applied. Multiple layers can be applied by continuous extrusion steps, wherein additional layers are added, or, using a suitable type of die, multiple layers can be added simultaneously. The cable can be placed in a wet curing environment, or allowed to cure under ambient conditions.

[0204] The test method involves 1 H NMR, TREF method, GPC method, and Cross-Fractionation Chromatograph (CFC) are well known in the art. For example, reference may be made to the disclosure of the prior document US20190119417A1.

[0205] Additional test methods include the following.

[0206]

[0207] Example

[0208] It should be understood that, although the invention has been described in conjunction with specific embodiments of the invention, the above description is intended to illustrate rather than limit the scope of the invention. Other aspects, advantages and improvements will be apparent to those skilled in the art to which the invention belongs.

[0209] Therefore, the following embodiments are presented in order to provide a complete disclosure and description to those skilled in the art and are not intended to limit the scope of what the inventors regard as their invention.

[0210] Components used in the examples:

[0211] LL7042, a linear low density polyethylene catalyzed by a Ziegler-Natta catalyst, with a melt index (MI) of 2 g / 10 min and a density of 0.918 g / cm 3 , from Sinopec LLDPE DFDA7042.

[0212] ExceedTM S9333, metallocene-catalyzed polyethylene with a melt index (MI) of 2 g / 10 min and a density of 0.925 g / cm 3 , molecular weight distribution (MWD) of 5.35, and composition distribution breadth index of 39.53 from ExxonMobil.

[0213] The polymer used in the example was first extruded and pelletized by TSE-40 at 195°C without adding any additives to obtain pellets. Then, the pellets obtained above were used for laboratory capillary rheometer (LCR) testing at 190°C. Such an operation simulates a two-step extrusion process. The following are all mass fractions.

[0214] Example 1

[0215] 100% LL7042 was subjected to a two-step extrusion process and its surface quality was evaluated, such as Figure 1 shown.

[0216] Example 2

[0217] The blends of 75% LL7042 and 25% S9333 were subjected to a two-step extrusion process and evaluated for their surface quality, as Figure 2 shown.

[0218] Example 3

[0219] The blends of 50% LL7042 and 50% S9333 were subjected to a two-step extrusion process and evaluated for their surface quality, as Figure 3 shown.

[0220] Example 4

[0221] The blends of 25% LL7042 and 75% S9333 were subjected to a two-step extrusion process and evaluated for their surface quality, as Figure 4 shown.

[0222] Example 5

[0223] 100% Exceed TM S9333 undergoes a two-step extrusion process and is evaluated for surface quality, such as Figure 5 shown.

[0224] In order to meet the above requirements for evaluating the surface quality of the blend, especially the surface smoothness, the applicant developed a test method by using image analysis. This test method is called the surface roughness test and the procedure is as follows.

[0225] 1. Use the image analysis software ImageJ (NIH, Bethesda, MD, USA; https: / / imagej.nih.gov / ij / , version 4.53e) to measure the grayscale value (yellow) along the middle line of the sample. The specific operation method is as follows:

[0226] 1. Use the line drawing tool to draw a reference line on the extruded spline. Note that this line needs to reflect the surface morphology of the entire spline and should be kept on the same side of the spline that does not reflect light. If this cannot be avoided, the length of the reference line can be shortened appropriately.

[0227] 2. In the software, use the Plot profile function to draw a distribution diagram of the image along the reference line and read the grayscale data from it.

[0228] 3. Calculate the standard deviation of the grayscale data.

[0229] In addition, the shear rate of 800S-1 of LCR test was used to compare the surface roughness. The test conditions of LCR were 195 degrees, L / D = 20 / 1, and the conclusions were as follows:

[0230]

[0231] 2. Calculate the standard deviation of the data. Smaller values ​​indicate better smoothness.

[0232] Results and discussion

[0233] The test data of the above embodiments are shown in Table 1 below.

[0234] Test Data

[0235]

[0236]

[0237] As shown in the table above, by gradually increasing the content of S9333 in the blend, the roughness grayscale STD of the blend obtained is gradually reduced, showing good consistency of decline. Specifically, when 25% of S9333 is added, the roughness grayscale of the blend is reduced by (11.5-10.6) / 11.5=7.83% relative to pure LL7042; when 50% of S9333 is added, the roughness grayscale of the blend is reduced by (11.5-5.5) / 11.5=52.17% relative to pure LL7042; when 75% of S9333 is added, the roughness grayscale of the blend is reduced by (11.5-3.9) / 11.5=66.09% relative to pure LL7042. In addition, when 50% of S9333 is added, the roughness grayscale of the blend is reduced by (8.5-5.5) / 8.5=35.29% relative to pure S9333; when 75% of S9333 is added, the roughness grayscale of the blend is reduced by (8.5-3.9) / 8.5=54.12% relative to pure S9333. The decrease in the roughness grayscale STD of the blend in the technical solution of the present application is unexpected.

[0238] Figure 1 The surface quality of pure LL7042 is shown. After the two-step extrusion process, the surface smoothness is poor, especially for high shear rate conditions (high line speed). When S9333 is added to the formulation, the applicant unexpectedly found that the surface smoothness can be greatly improved.

[0239] Figure 2 , 3 and 4 show the surface quality at different S9333 addition amounts. When the S9333 addition amount is 25%, the LCR results clearly show that the improvement in surface quality begins to appear. From the results, it is found that the higher the S9333 addition amount, the better the surface quality improvement can be obtained. However, when pure Exceed S9333 is used ( Figure 5 ), the surface quality obtained cannot be as good as the corresponding blend. Such results show that the combination of linear low-density polyethylene catalyzed by Ziegler-Natta catalyst and metallocene-catalyzed polyethylene in the technical solution of the present invention, such as S9333+LL7042, is an ideal solution to achieve both surface quality and cost effectiveness. Although the surface smoothness is not as good as 100% S9333 after adding 25% S9333, considering the cost factor, mixing 25% S9333 is still an economical choice to improve surface smoothness and maintain other mechanical properties.

[0240] Unless otherwise specified, the phrase "consisting essentially of" does not exclude the presence of other steps, elements or materials (whether or not specifically mentioned in the specification), provided that these steps, elements or materials do not affect the basic and novel characteristics of the invention, and further, they do not exclude impurities and variations normally associated with the elements and materials used.

[0241] For simplicity, only some numerical ranges are clearly disclosed herein. However, a certain lower limit can be used in combination with any other upper limit to limit the scope that is not clearly recorded. Similarly, a certain lower limit can be used in combination with any other lower limit to limit the scope that is not clearly recorded. Similarly, a certain upper limit can also be used in combination with any upper limit to limit the scope that is not clearly recorded. In addition, even if there is no clear description, each point or individual value between the two end points is also included in the scope. Therefore, each point or individual value itself can be used as a lower limit or upper limit in combination with other points or individual values ​​or other lower or upper limits to limit the scope that is not clearly recorded.

[0242] All prior art documents are incorporated herein by reference, provided that their disclosure does not contradict the description of the present invention. In addition, all documents and references (including test procedures, publications, patents, journal articles, etc.) cited herein are incorporated herein by reference, provided that their disclosure does not contradict the description of the present invention.

[0243] While the invention has been described in terms of numerous embodiments and examples, those skilled in the art, after reading this disclosure, will appreciate that other embodiments can be devised without departing from the scope and spirit of the invention disclosed herein.

Claims

1. A polyethylene blend comprising a linear low-density polyethylene catalyzed by a Ziegler-Natta catalyst and a metallocene-catalyzed polyethylene, wherein the metallocene-catalyzed polyethylene has a melt index (MI) of 0.1 g / 10 min to 30 g / 10 min and a density of 0.890 g / cm 3 Up to 0.940g / cm 3 , a molecular weight distribution (MWD) of 2 to 12, and a composition distribution width index of 10 to 50, and the roughness grayness of the polyethylene blend is reduced by 35-70% relative to the linear low density polyethylene catalyzed by a pure Ziegler-Natta catalyst, and / or reduced by 12-58% relative to the polyethylene catalyzed by a pure metallocene catalyst.

2. The polyethylene blend according to claim 1, wherein the metallocene-catalyzed polyethylene comprises at least 65 wt% ethylene-derived units and 0-35 wt% C3-C 12 Olefin comonomer-derived units, based on the total weight of the metallocene-catalyzed polyethylene; wherein the metallocene-catalyzed polyethylene further has: a) RCI,m of 100 kg / mol or more; and one or both of the following: b) a Tw1-Tw2 value of -16 to -38°C; and c) a Mw1 / Mw2 value of at least 0.9; and one or more of the following: d) Melt index ratio (I) of 10-90 21 / I2); e) Mz / Mw of 2.5-5.0; f) Mz / Mn of 10-40; and g) 0.900 or greater g' (vis) .

3. The polyethylene blend according to any one of the preceding claims, wherein the metallocene-catalyzed polyethylene comprises 0.5-20 wt% of C3-C 12 Olefin comonomer-derived units are based on the total weight of the metallocene-catalyzed polyethylene.

4. The polyethylene blend according to any one of the preceding claims, wherein the metallocene-catalyzed polyethylene comprises 1 to 10 wt% of C4-C8 α-olefin comonomer-derived units, based on the total weight of the metallocene-catalyzed polyethylene.

5. The polyethylene blend according to any one of the preceding claims, wherein the metallocene-catalyzed polyethylene has a melt index (MI) of 0.1 g / 10 min to 6 g / 10 min.

6. The polyethylene blend of any one of the preceding claims, wherein the metallocene-catalyzed polyethylene has a melt index ratio (MIR) of 20-45. 21 / I2).

7. The polyethylene blend according to any one of the preceding claims, wherein the metallocene-catalyzed polyethylene has a high load melt index (MLI) of 5 to 40 g / 10 min. 21 ).

8. The polyethylene blend according to any one of the preceding claims, wherein the metallocene-catalyzed polyethylene has a Mw / Mn of 5 to 10.

5.

9. The polyethylene blend of any one of the above claims, wherein the metallocene-catalyzed polyethylene has a g'(vis) of 0.940 or greater.

10. The polyethylene blend according to any one of the preceding claims, wherein the metallocene-catalyzed polyethylene has a molecular weight of 0.900 g / cm 3 -0.930g / cm 3 density.

11. The polyethylene blend according to any one of the preceding claims, wherein the metallocene-catalyzed polyethylene has a melt index (MI) of 2 g / 10 min, a density of 0.925 g / cm 3 , molecular weight distribution (MWD) is 5.35, and composition distribution breadth index is 39.

53.

12. The polyethylene blend according to any one of the preceding claims, wherein the Ziegler-Natta catalyst-catalyzed linear low density polyethylene has a melt index (MI) of 2 g / 10 min and a density of 0.918 g / cm 3 .

13. The polyethylene blend according to any one of the preceding claims, wherein the content of the metallocene-catalyzed polyethylene is 40 wt% to 80 wt%, preferably 45 wt% to 75 wt%, preferably 50 wt% to 75 wt%, more preferably 55 wt% to 70 wt%, based on the total weight of the polyethylene blend.

14. The polyethylene blend according to any one of the preceding claims, wherein the content of the linear low density polyethylene catalyzed by the Ziegler-Natta catalyst is 60 wt% to 20 wt%, preferably 55 wt% to 25 wt%, preferably 50 wt% to 25 wt%, more preferably 45 wt% to 30 wt%, based on the total weight of the polyethylene blend.

15. Use of a metallocene-catalyzed polyethylene for improving the surface quality of a blend comprising a linear low-density polyethylene catalyzed by a Ziegler-Natta catalyst, wherein the metallocene-catalyzed polyethylene has a melt index (MI) of 0.1 g / 10 min to 30 g / 10 min, a density of 0.890 g / cm 3 Up to 0.940g / cm 3 , a molecular weight distribution (MWD) of 2 to 12, and a composition distribution width index of 10 to 50, and the roughness grayness of the polyethylene blend is reduced by 35-70% relative to the linear low density polyethylene catalyzed by a pure Ziegler-Natta catalyst, and / or reduced by 12-58% relative to the polyethylene catalyzed by a pure metallocene catalyst.

16. A polyethylene blend comprising 50 wt% to 75 wt% of a metallocene-catalyzed polyethylene and 50 wt% to 25 wt% of a linear low density polyethylene catalyzed by a Ziegler-Natta catalyst, based on the total weight of the polyethylene blend, wherein the metallocene-catalyzed polyethylene has a melt index (MI) of 0.1-6 g / 10 min, preferably 2 g / 10 min, a density of 0.900-0.930 g / cm 3 , preferably 0.925 g / cm 3 , a molecular weight distribution (MWD) of 5-10.5, preferably 5.35, and a composition distribution width index of 10 to 50, preferably 39.53, wherein the linear low density polyethylene catalyzed by the Ziegler-Natta catalyst has a melt index (MI) of 0.5-2.5 g / 10 min, preferably 2 g / 10 min and a density of 0.905-0.930 g / cm 3 , preferably 0.918 g / cm 3 .

Citation Information

Patent Citations

  • Process for preparing polyethylene blend comprising metallocene produced resins and Ziegler-Natta produced resins

    CN103502349A

  • Very low density polyethylene blends

    CN1535296A

  • Physical blends of polyethylenes

    CN1596284A

  • Polyethylene blend for a film layer

    EP4417629A1

  • Polyethylene blends with good contact transparency

    US20050222338A1